Battery, accumulator and battery separator thereof

CN123018350APending Publication Date: 2026-10-30DARAMIC LLC
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610820520.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2018-04-20
Filing Date
2019-04-18
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

随着越来越多的活性材料从电极上脱落,该电极的效率越来越低,电池的性能和寿命也随之降低

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123018350A_ABST
    Figure CN123018350A_ABST
Patent Text Reader

Abstract

A battery has a fiber mat tensile strength in the machine direction of 200 N / 50 mm and a tensile strength across the machine direction of 150 N / 50 mm. Yet another embodiment: silanol groups convert the silica structure from a crystalline structure to an amorphous structure. Still another embodiment: shish-kebab structures are formed within the polyolefin. Other embodiments: the negative plate is encapsulated by a fiber mat, the porous membrane encapsulates an adjacent positive. Further embodiments: the fiber mat is at least partially integrated into the negative plate, the porous membrane is either encapsulated around the negative plate into which the fiber mat is partially integrated or encapsulated by an adjacent positive plate. Another embodiment: the negative plate is encapsulated by a porous membrane having ribs, a fiber mat is present between the encapsulated negative plate and the porous membrane encapsulating the negative plate. A simple embodiment: a discrete array of back web tilted ribs is in contact with an electrode. According to the invention, the battery is operated in a partially charged state, acid stratification can be inhibited.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This application is a divisional application. The original international application number was PCT / US2019 / 028024; the original priority date was April 20, 2018; the original international application date was April 18, 2019; the date of entry into the Chinese national phase was December 17, 2020, and the Chinese application number was 201980040662.2; the original invention title was "Acid Battery with Fiber Pad". Cross-referencing related patent applications

[0002] This application claims priority and benefit to co-pending French patent application 1853502, filed on April 20, 2018, the entire contents of which are incorporated herein by reference. Technical Field

[0003] According to at least selected embodiments, this disclosure or invention is directed to new or improved separators, battery separators, flooded battery separators, enhanced flooded battery separators, fiber pads, batteries, battery cells, and / or methods of manufacturing and / or using such separators, battery separators, fiber pads, flooded battery separators, enhanced flooded battery separators, battery cells, and / or batteries. According to at least specific embodiments, this disclosure or invention is directed to new or improved enhanced flooded battery separators and fiber pads for start-up lighting ignition (SLI) batteries, flooded batteries for deep-cycle applications, flooded batteries for power applications, flooded batteries for partial state-of-charge (PSoC) applications, and / or enhanced flooded batteries and / or systems, vehicles, etc. (which include such separators, fiber pads, and batteries), and / or improved methods of manufacturing and / or using such improved separators, fiber pads, battery cells, batteries, systems, vehicles, etc. According to at least certain embodiments, this disclosure or invention is dedicated to improved separators for enhanced flooded batteries and / or improved methods of manufacturing and / or using such batteries having such improved separators. According to at least selected embodiments, this disclosure or invention is dedicated to separators, particularly separators for enhanced flooded batteries, which have reduced resistance and / or increased cold-start current. Furthermore, methods, systems, and battery separators disclosed herein are used to improve active material retention, increase battery life, reduce water consumption, reduce internal resistance, increase wettability, reduce acid stratification, improve acid diffusion, increase cold-start current, and improve uniformity, at least in enhanced flooded batteries and / or the like. According to at least particular embodiments, this disclosure or invention is dedicated to improved separators for enhanced flooded batteries, wherein said separators include one or more performance-enhancing additives or coatings, optimized porosity, optimized void volume, amorphous silica, silica with higher oil absorption, silica with higher silanol groups, retention and / or improved retention of active materials on electrodes, and / or any combination thereof.

[0004] According to at least selected embodiments, this disclosure or invention is directed to separators for lead-acid batteries (particularly flooded lead-acid batteries) and various lead-acid batteries having such separators (e.g., flooded lead-acid batteries or enhanced flooded lead-acid batteries). According to at least selected embodiments, this disclosure or invention is directed to new or improved separators, battery cells, batteries, and / or methods of manufacturing and / or using such separators, battery cells, and / or batteries. According to at least specific embodiments, this disclosure or invention is directed to improved separators for lead-acid batteries and / or improved methods of using such batteries having such improved separators. Furthermore, this document discloses methods, systems, and battery separators for improving the retention of active materials in lead-acid batteries, extending battery life, reducing battery failures, reducing water consumption, improving oxidation stability, increasing, maintaining, and / or reducing float charge current, increasing end-of-charge (EOC) current, reducing the current and / or voltage required for deep-cycle charging and / or full charging, minimizing the increase in internal resistance, reducing resistance, increasing wettability, reducing electrolyte wetting time, reducing battery formation time, reducing antimony poisoning, reducing acid stratification, improving acid diffusion, and / or improving uniformity. According to at least a particular embodiment, this disclosure or invention is dedicated to improved separators for lead-acid batteries, wherein said separators comprise one or more improved performance-enhancing additives and / or coatings. According to at least certain embodiments, the disclosed separator can be used in deep-cycle applications, such as in moving machinery or vehicles and / or stationary machinery or vehicles, such as golf carts (also referred to as "golf carts"), forklifts, inverters, renewable energy systems and / or alternative energy systems (e.g., solar power systems and wind power systems, by way of example only); in particular, the disclosed separator is useful in battery systems in which deep-cycle and / or partial-charge operation is part of the battery life; even more particularly, it is useful in such battery systems in which additives and / or alloys [e.g., antimony (Sb)] are added to the battery to improve battery life and / or performance and / or enhance the battery's ability to operate in deep-cycle and / or partial-charge states.

[0005] According to at least selected embodiments, this disclosure is dedicated to improved lead-acid batteries (such as flooded lead-acid batteries), including improved systems for lead-acid batteries, and / or battery separators, improved battery separators, improved vehicles including such systems, methods of manufacturing or using such systems, or combinations thereof. According to at least specific embodiments, this disclosure or invention is dedicated to new or improved flooded lead-acid batteries, improved battery separators for such batteries, and / or methods of manufacturing, testing, and using such improved flooded lead-acid batteries, and / or combinations thereof. Additionally, methods, systems, batteries, and / or battery separators disclosed herein are used to reduce acid stratification and improve battery life and performance in flooded lead-acid batteries and such batteries operating in a partially charged state. Background Technology

[0006] A battery separator electrically isolates the positive (or positive plate) and negative (or negative plate) terminals of a battery to prevent short circuits. Such separators are typically microporous and ion-conducting, allowing ions to pass between the positive and negative terminals. Separators can be made of polyolefins, such as polyethylene. In lead-acid batteries (e.g., automotive and / or industrial and / or deep-cycle batteries), the separator is typically a microporous polyethylene separator; in some cases, such a separator may include a back mesh and multiple ribs on one or both sides of the back mesh. See *Battery Materials Handbook* (Besenhard, JO, editor, Wiley-VCH Verlag GmbH, Weinheim, Germany (1999), Chapter 9, pp. 245-292).

[0007] To meet the growing power demands in Idle Start-Stop (ISS) applications, enhanced flooded battery (EFB) and absorbed glass mat (AGM) batteries have been developed. EFB systems have an architecture similar to conventional flooded lead-acid batteries, where the positive and / or negative electrodes are surrounded by microporous separators and immersed in a liquid electrolyte. AGM systems, on the other hand, do not contain a free liquid electrolyte. Instead, the electrolyte is absorbed into a glass fiber mat laminated onto the electrodes. Historically, AGM systems have offered higher discharge power, better cycle life, and greater cold-start current compared to flooded battery systems. However, AGM batteries are significantly more expensive to manufacture and are more sensitive to overcharging. Thus, EFB systems remain an attractive option for both mobile and stationary power sources in a variety of markets and applications.

[0008] An EFB system may include one or more battery separators that separate or isolate the positive and negative electrodes within a lead-acid battery cell. The battery separator likely has two main functions. First, it should maintain physical separation between the positive and negative electrodes to prevent any current from flowing between them—which would cause a short circuit. Second, it should allow ion flow between the positive and negative electrodes with the least possible resistance. Battery separators can be made from many different materials; however, separators made of porous, non-conductive materials have proven well to fulfill these two opposing functions. With this structure, the pores facilitate ion diffusion between the electrodes, while the non-conductive polymer mesh prevents short circuits.

[0009] EFBs, with their improved discharge rate and cold start current (CCA), will be able to replace AGM batteries. Cold start current is related to the battery's internal resistance. It is expected that reducing the internal resistance of enhanced flooded batteries will improve the CCA rating. Therefore, new battery separators and / or battery technologies are needed to address and overcome the challenges posed by current lead-acid battery systems, particularly in reducing internal resistance and improving cold start current in enhanced flooded batteries.

[0010] To reduce fuel consumption and emissions, automakers have implemented varying degrees of hybrid electric vehicles. One form of hybrid electric vehicle (HEV) is sometimes referred to as a “micro HEV” or “micro hybrid.” In such micro HEVs or similar vehicles, the car may have an idle start-stop (ISS) function, where the engine can shut off at different points during idle start-stop and / or regenerative braking. While this increases the vehicle’s fuel economy, it also increases the strain on the battery, which must power auxiliary devices such as air conditioning, media players, etc., when the vehicle is not in motion.

[0011] Conventional vehicles (such as cars without start-stop functionality) can use conventional flooded lead-acid batteries, such as starter light ignition (SLI) lead-acid batteries. Because the engine is never turned off during use, energy is only drawn from the battery when the engine is started or running. Thus, the battery is typically in an overcharged state rather than a partially charged state. For example, such a conventional flooded lead-acid battery can be in a state of charge greater than 95%, greater than 96%, greater than 97%, greater than 98%, greater than 99%, or even greater than 100% because it is frequently overcharged. During overcharging, bubbles (e.g., hydrogen bubbles) are generated within the conventional lead-acid battery, and these circulating bubbles act to mix the liquid electrolyte (e.g., sulfuric acid) within the battery.

[0012] On the other hand, ISS vehicles continuously draw energy from the battery, so the battery is always in a partially charged state. In a partially charged state, no bubbles are generated, and the internal mixing of the electrolyte is greatly reduced, leading to acid stratification within the battery. Therefore, acid stratification is a problem in various enhanced flooded batteries operating in a partially charged state (such as idle-start-stop flooded lead-acid batteries). However, for most conventional or traditional flooded lead-acid batteries operating in overcharged, fully charged, or near-fully charged states, acid stratification is not a problem at all.

[0013] Acid stratification is a term used to describe a process in which water and sulfuric acid in the electrolyte separate, with the denser sulfuric acid accumulating at the bottom of the battery and correspondingly resulting in a higher water content at the top. Acid stratification is undesirable in flooded lead-acid batteries (such as enhanced flooded lead-acid batteries or start / stop flooded lead-acid batteries). Reduced acid levels at the top of the electrodes can impede uniformity and charge acceptability within the battery system and may increase internal resistance variations along the battery height from top to bottom. Increased acid levels at the bottom of the battery artificially raise the battery voltage, which can interfere with the battery management system and potentially send unintentional / erroneous health status signals. Overall, acid stratification leads to higher resistance across different parts of the battery, which can cause electrode problems and / or shorten battery life. Given the increasing prevalence of start / stop batteries and / or other enhanced flooded lead-acid batteries in hybrid and all-electric vehicles aimed at improving fuel efficiency and reducing emissions, solutions to reduce acid stratification and / or improve acid mixing are in high demand.

[0014] In some cases, valve-regulated lead-acid (VRLA) technology can be used to reduce acid stratification to some extent. In this technology, the acid is immobilized by a gel electrolyte and / or absorbed glass mat (AGM) battery separator system. Unlike the free-flowing electrolyte in flooded lead-acid batteries, the electrolyte in VRLA / AGM batteries is absorbed onto fibers or fibrous materials, such as glass fiber mats, polymer fiber mats, gel electrolytes, etc. However, VRLA / AGM battery systems are significantly more expensive to manufacture than flooded battery systems. In some cases, VRLA / AGM technology may be more sensitive to overcharging, may dry out under high heat, may experience a gradual decrease in capacity, and may have a lower energy density. Similarly, in some cases, gel VRLA technology may have higher internal resistance and may have reduced charge acceptability.

[0015] In an EFB system, the electrode or plate consists of a lead alloy grid and active material. During the manufacturing process of such an EFB, a slurry of active material is coated onto the lead alloy grid and cured to form the electrode or plate. The slurry may include one or more of carbon black, barium sulfate, lignin sulfonate, sulfuric acid, and water. The curing process transforms the slurry into a mixture of lead sulfate, which becomes the electrochemical active material during the initial charging of the battery. The slurry on the positive electrode is called the positive electrode active material (PAM). Similarly, the active material on the negative electrode is called the negative electrode active material (NAM). During the charge and discharge cycles of the battery, the electrodes undergo expansion and contraction. Over time, this deformation of the electrodes causes the active material to detach from the electrodes and physically separate from them. As more and more active material detaches from the electrodes, the efficiency of the electrode decreases, and the performance and lifespan of the battery also decrease. Therefore, new battery separators and / or battery technologies are needed to address and overcome the challenges posed by current lead-acid battery systems, particularly preventing or stopping the detachment of active material from the electrodes in enhanced flooded lead-acid batteries.

[0016] For at least certain applications or batteries, improved separators are still needed to provide longer cycle life, reduced antimony poisoning, reduced water consumption, reduced float current for full charge, and / or reduced voltage. More specifically, improved separators and improved batteries incorporating improved separators (e.g., those operating in a partially charged state and / or deep-cycle batteries) are still needed to provide extended battery life in lead-acid batteries, reduced battery failure, reduced water consumption, improved oxidation stability, improved, maintained, and / or reduced float current, improved end-of-charge (EOC) current, reduced current and / or voltage required to charge and / or fully charge the battery (e.g., deep-cycle batteries), minimized increase in internal resistance, reduced resistance, increased wettability, reduced electrolyte wetting time, reduced battery formation time, reduced acid stratification, improved acid diffusion, and / or improved uniformity. Summary of the Invention

[0017] According to at least selected embodiments, this disclosure or invention can solve the above-mentioned problems or difficulties, particularly but not limited to EFB batteries and separators, and / or can provide or can be committed to new or improved separators, battery separators, membranes, separator membranes, enhanced flooded battery separators, fiber pads, batteries, battery cells and / or methods of manufacturing and / or using such separators, battery separators, fiber pads, enhanced flooded battery separators, battery cells and / or batteries. According to at least specific embodiments, this disclosure or invention is committed to new or improved flooded lead-acid battery separators and fiber pads for start-up lighting ignition (SLI) batteries, flooded batteries and / or enhanced flooded batteries and / or systems for deep cycle applications, vehicles and / or the like (which include such separators, pads, batteries) and / or improved methods of manufacturing and / or using such improved separators, pads, battery cells, batteries, systems, vehicles and / or the like. According to at least certain embodiments, this disclosure or invention is dedicated to improved separators for enhanced flooded batteries and / or improved methods of manufacturing and / or using such batteries having such improved separators. According to at least selected embodiments, this disclosure or invention is dedicated to separators, particularly separators for enhanced flooded batteries having reduced resistance and / or increased cold-start current. Additionally, methods, systems, and battery separators disclosed herein are used to improve the retention of active materials, extend battery life, reduce water consumption, reduce internal resistance, increase wettability, reduce acid stratification, improve acid diffusion, improve cold-start current, and improve uniformity in at least enhanced flooded batteries and / or similar types. According to at least particular embodiments, this disclosure or invention is dedicated to improved separators for enhanced flooded batteries, wherein the separator comprises one or more performance-enhancing additives or coatings, optimized porosity, optimized void volume, amorphous silica, silica with higher oil absorption, silica with higher silanol groups, retention and / or improved retention of active materials on the electrodes, and / or any combination thereof.

[0018] According to at least selected embodiments, this disclosure or invention is dedicated to separators for lead-acid batteries (particularly flooded lead-acid batteries) and various different lead-acid batteries having such separators (e.g., flooded lead-acid batteries or enhanced flooded lead-acid batteries). According to at least selected embodiments, this disclosure or invention is dedicated to new or improved separators, battery cells, batteries, and / or methods of manufacturing and / or using such separators, battery cells, and / or batteries. According to at least specific embodiments, this disclosure or invention is dedicated to improved separators for lead-acid batteries and / or improved methods of using such batteries having such improved separators. Additionally, methods, systems, and battery separators disclosed herein are used to enhance the retention of active materials in lead-acid batteries, extend battery life, reduce battery failure, reduce water consumption, improve oxidation stability, improve, maintain, and / or reduce float charge current, improve end-of-charge (EOC) current, reduce the current and / or voltage required for deep-cycle charging and / or full charging, minimize the increase in internal resistance, reduce resistance, and increase wettability. This invention aims to reduce electrolyte wetting time, reduce battery formation time, reduce antimony poisoning, reduce acid stratification, improve acid diffusion, and / or improve uniformity. According to at least certain embodiments, this disclosure or invention is dedicated to improved separators for lead-acid batteries, wherein the separator comprises one or more improved performance-enhancing additives and / or coatings. According to at least certain embodiments, the disclosed separator can be used in deep-cycle applications, such as in moving machinery or vehicles and / or stationary machinery or vehicles, like golf carts, forklifts, inverters, renewable energy systems, and / or alternative energy systems, by way of example only, such as solar power systems and wind power systems; particularly, the disclosed separator is useful in battery systems where deep-cycle and / or partial-charge operation is part of the battery life; even more particularly, it is useful in such battery systems where additives and / or alloys [e.g., antimony (Sb)] are added to the battery to improve battery life and / or performance and / or enhance the battery's deep-cycle and / or partial-charge operation capabilities.

[0019] According to at least selected embodiments, this disclosure is directed to improved lead-acid batteries (such as flooded lead-acid batteries), including improved systems for lead-acid batteries, and / or battery separators, improved vehicles including such systems, methods of manufacturing or using such systems, or combinations thereof. According to at least specific embodiments, this disclosure or invention is directed to new or improved flooded lead-acid batteries, improved battery separators for such batteries, and / or methods of manufacturing, testing, and using such improved flooded lead-acid batteries, and / or combinations thereof. Additionally, methods, systems, batteries, and / or battery separators disclosed herein are used to reduce acid stratification and improve battery life and performance in flooded lead-acid batteries and such batteries operating in a partially charged state.

[0020] Separators made of polyolefins, such as polyethylene, typically contain silica to facilitate wetting of the separator by the hydrophilic electrolyte. In some cases, a hydrophilic material, such as a fiber pad, is placed adjacent to the separator to aid in wetting and retaining the active material coated on the positive electrode. Similarly, a fiber pad can be placed to retain the active material on the negative electrode.

[0021] This application also addresses new and improved lead-acid batteries and vehicles incorporating these new and improved lead-acid batteries. The flooded lead-acid battery exhibits reduced acid stratification, a problem that, if severe enough, can render the battery unusable. In addition to exhibiting reduced acid stratification, the flooded lead-acid battery described herein also exhibits other desirable performance characteristics, such as improved charge acceptance.

[0022] In one aspect, a flooded lead-acid battery with an electrode array is described, the array being configured to have one or more negative electrodes or negative electrode plates and one or more positive electrodes or positive electrode plates, the positive and negative electrodes being alternately arranged and facing each other respectively. In this electrode array, at least one negative electrode is wrapped with at least one of a woven material and a nonwoven material. A ribbed or unribbed porous membrane wraps the adjacent positive electrode (the positive electrode adjacent to at least one wrapped negative electrode).

[0023] In some embodiments where the negative electrode is wrapped in a woven material, the woven material may be at least one selected from extrudable mesh, woven glass pad, and carbon fiber woven material.

[0024] In other embodiments where the negative electrode is encapsulated by a nonwoven material, the nonwoven material may be formed from at least one material selected from glass, pulp, polymers, and combinations thereof. In embodiments where the nonwoven material is formed from a polymer, it may be formed solely from the polymer or in combination with glass and / or pulp. The polymer may be at least one selected from polyolefins, polyesters, polyamides, polyimides, and combinations thereof. In some embodiments, in addition to at least one of glass, pulp, polymers, and combinations thereof, the nonwoven material may also be provided with an inorganic powder. The inorganic powder may be silica. In some embodiments, the nonwoven material may be a spunbond melt-woven composite material. In some embodiments, the nonwoven material is a carbon fiber nonwoven material.

[0025] In some embodiments, the porous membrane may be ribbed. The porous membrane may have ribs on one or both sides. The ribs have a height of about 10 μm to about 200 μm. In some embodiments, the porous membrane may be unribbed. Whether the porous membrane is ribbed or unribbed, it may be made of at least one natural or synthetic material selected from polyolefins, phenolic resins, polyvinyl chloride (PVC), rubber, synthetic wood pulp, glass fiber, cellulose fiber, or combinations thereof.

[0026] In some embodiments, the porous membrane may be configured to contain polyethylene, silica, and residual or unextracted processing oil.

[0027] In some embodiments, one or more, two or more, or three but not four sides of the positive electrode encased in a porous membrane are sealed. In some embodiments, one or more, two or more, or three but not four sides of the negative electrode encased in a fiber pad are sealed.

[0028] On the other hand, a flooded lead-acid battery with an electrode array is described, the array being configured to have one or more negative electrodes and one or more positive electrodes, the positive and negative electrodes being alternately arranged and facing each other. In this array, a fiber pad is at least partially integrated into the negative electrode. Additionally, in this embodiment, a ribbed or unribbed porous membrane encapsulates the fiber pad partially integrated into the negative electrode or adjacent positive electrode. In some embodiments, 2% to 50% of the fiber pad is integrated into the negative electrode. In some embodiments, 5% to 25% of the fiber pad is integrated into the negative electrode. In some embodiments, 5% to 20% of the fiber pad is integrated into the negative electrode. In some embodiments, 10% to 15% of the fiber pad is integrated into the negative electrode.

[0029] In some embodiments, the woven material is at least partially integrated into the negative electrode. The woven material may be at least one selected from extrudable webs, woven glass pads, and carbon fiber woven materials.

[0030] In some embodiments, the nonwoven material is at least partially integrated into the negative electrode. The nonwoven material can be formed from at least one material selected from glass, pulp, polymers, and combinations thereof. In embodiments where the nonwoven material is formed from a polymer, the polymer can be used alone or in combination with at least glass and / or pulp. The polymer can be at least one selected from polyolefins, polyesters, polyamides, polyimides, and combinations thereof. In some embodiments, in addition to at least one material selected from glass, pulp, polymers, and combinations thereof, the nonwoven material can also be provided with an inorganic powder. The inorganic powder can be silica. In some embodiments, the nonwoven material can be a spunbond melt-spun composite material. In some embodiments, the nonwoven material is a carbon fiber nonwoven material.

[0031] In some embodiments, the porous membrane may be ribbed. The porous membrane may have ribs on one or both sides. The ribs have a height of about 10 μm to about 200 μm. In some embodiments, the porous membrane may be unribbed. Whether the porous membrane is ribbed or unribbed, it may be made of at least one natural or synthetic material selected from polyolefins, phenolic resins, polyvinyl chloride (PVC), rubber, synthetic wood pulp, glass fiber, cellulose fiber, or combinations thereof. In some embodiments, the porous membrane contains polyethylene, silica, and residual or unextracted processing oil.

[0032] In some embodiments, one or more, two or more, or three but not four sides of a porous membrane encapsulating the fiber pad, which is at least partially integrated into the negative electrode or adjacent to the positive electrode, are sealed.

[0033] On the other hand, a liquid-filled lead-acid battery with an electrode array is described, the array having one or more negative electrodes and one or more positive electrodes, the positive and negative electrodes being arranged alternately and facing each other respectively. In some embodiments, the negative electrode of the electrode array is wrapped with a porous membrane having ribs on at least one side, and a fiber pad exists between the wrapped negative electrode and the porous membrane wrapping the negative electrode. In some preferred embodiments, the ribs of the porous membrane are at least on the side of the porous membrane closest to the fiber pad. The ribs of the porous membrane, whether present on the side of the porous membrane closest to the fiber pad or on the opposite side, can have a height of 5 μm to 300 μm or 25 μm to 200 μm.

[0034] In some embodiments, in addition to being encapsulated by a porous membrane, the encapsulated negative electrode is also encapsulated with a fiber pad. In some embodiments, a nonwoven or woven material is at least partially integrated into the encapsulated negative electrode. In some embodiments, the nonwoven or woven material is present between the ribs of the porous membrane. In embodiments where the nonwoven or woven material is present between the ribs of the porous membrane, the nonwoven or woven material has a thickness of 50% to 150% of the rib height.

[0035] In some embodiments, a woven material is present between the wrapped negative electrode and the porous membrane encapsulating the electrode. In such embodiments, the woven material is at least one selected from extrudable mesh, woven glass pads, and carbon fiber woven materials.

[0036] In some embodiments, a nonwoven material is present between the wrapped negative electrode and the porous membrane encapsulating the electrode. Sometimes, the nonwoven material is formed of at least one material selected from glass, pulp, polymers, and combinations thereof. In embodiments where a polymer is present alone in the nonwoven material, or in combination with glass and / or pulp, or in combination with another material, the polymer is at least one selected from polyolefins, polyesters, polyamides, polyimides, and combinations thereof. In some embodiments, in addition to having at least one of glass, pulp, polymers, and combinations thereof, the nonwoven material may also contain an inorganic powder. The inorganic powder may be silica. In some embodiments, the nonwoven material may be a spunbond melt-spun composite material. In some embodiments, the nonwoven material is a carbon fiber nonwoven material.

[0037] In some embodiments described herein, the porous membrane may have ribs on both sides. The porous membrane may be made of at least one natural or synthetic material selected from polyolefins, phenolic resins, polyvinyl chloride (PVC), rubber, synthetic wood pulp, glass fiber, cellulose fiber, or combinations thereof. In some embodiments, the porous membrane contains polyethylene, silica, and residual or unextracted processing oil. In some embodiments, one or more, two or more, or three but not four sides of the porous membrane surrounding the negative electrode may be sealed.

[0038] In some implementations, one or more, two or more, or three but not four sides of the fiber pad wrapped around the negative electrode can be sealed.

[0039] On the other hand, this article describes vehicles with one or more flooded lead-acid batteries, including start / stop vehicles.

[0040] In a first exemplary embodiment, the lead-acid battery includes an electrode array having one or more negative electrodes and one or more positive electrodes interleaved between the negative electrodes. At least one of the negative electrodes is encapsulated by a fiber pad, while the one or more positive electrodes adjacent to at least one of the negative electrodes are encapsulated by a porous membrane. The porous membrane may be a microporous battery separator.

[0041] In an exemplary aspect, the fiber mat may be nonwoven, mesh, felt, and / or combinations thereof. The fiber mat may also be glass fiber, pulp, polymer, and / or combinations thereof. Additionally, the fiber mat may be formed from a polymer and additional glass fiber, pulp, and / or combinations thereof, and the polymer may be polyolefin, polyester, polyamide, polyimide, and / or combinations thereof. The fiber mat may be an inorganic material, such as silica. The fiber mat may be a spunbond melt nonwoven composite material or a carbon fiber nonwoven material and / or the like.

[0042] An exemplary porous membrane may be provided with one or more sets of ribs on at least one surface, or one or more sets of ribs on both surfaces. The ribs may have a height of about 10 μm to about 2.0 mm. The porous membrane may be one or more of natural materials, synthetic materials, polyolefins, phenolic resins, polyvinyl chloride (PVC), natural rubber, synthetic rubber, synthetic wood pulp, glass fiber, lignin, cellulose fibers, and / or combinations thereof. Alternatively, the porous membrane may be polyethylene, silica, and processing oil, wherein the amount of processing oil is about 5% to about 15% of the weight of the porous membrane.

[0043] In specific selected aspects, the porous membrane has a porosity greater than about 55%, about 60%, and about 65%.

[0044] In another exemplary aspect, the porous membrane of the exemplary lead-acid battery may be encapsulated around the positive electrode and sealed on one, two, and / or three sides of the positive electrode.

[0045] In yet another exemplary aspect, the fiber pad of the exemplary lead-acid battery may be encapsulated around the negative electrode and sealed on one, two, and / or three sides of the negative electrode.

[0046] In yet another exemplary embodiment, a preferred example of a lead-acid battery may be provided with an electrode array including one or more negative electrodes and one or more positive electrodes interspersed between the one or more negative electrodes. The battery may further include one or more electrode and fiber pad assemblies, comprising a fiber pad at least partially integrated into at least one negative electrode. A porous membrane (which may be a microporous membrane) may encapsulate one or more of the one or more electrode and fiber pad assemblies, or may encapsulate at least one of the one or more positive electrodes adjacent to the one or more electrode and fiber pad assemblies. In an exemplary aspect, the fiber pad may be integrated into the active material at about 2% to about 50% of the fiber pad thickness, about 5% to about 25% of the pad thickness, about 5% to about 20% of the pad thickness, or about 10% to about 15% of the pad thickness.

[0047] Any exemplary fiber mat can be one or more of nonwoven materials, meshes, felts, and / or combinations thereof. Additionally, the fiber mat can be one or more of glass fibers, pulp, polymers, and / or combinations thereof. Further, the fiber mat can be formed from polymers and polymers combined with additional glass fibers, pulp, and / or combinations thereof, and the polymer can be polyolefins, polyesters, polyamides, polyimides, and / or combinations thereof.

[0048] In another aspect of the exemplary lead-acid battery, the exemplary fiber pad can be an inorganic material, such as silica. The fiber pad can be spunbond melt nonwoven fabric, carbon fiber nonwoven fabric, and / or the like.

[0049] In another aspect of the exemplary lead-acid battery, the exemplary porous membrane may have one or more sets of ribs on one or both of its surfaces. The ribs in the one or more sets of ribs may have a height of about 10 μm to about 2.0 mm.

[0050] Exemplary porous membranes may be at least one of natural materials, synthetic materials, polyolefins, phenolic resins, polyvinyl chloride (PVC), natural rubber, synthetic rubber, synthetic wood pulp, glass fiber, lignin, cellulose fiber, and / or combinations thereof. In a particular embodiment, the porous membrane may be polyethylene, silica, and processing oil.

[0051] In another exemplary aspect, the porous membrane of the exemplary lead-acid battery may be encapsulated around the positive electrode and sealed on one, two, and / or three sides of the positive electrode. In yet another exemplary aspect, the porous membrane of the exemplary lead-acid battery may be sealed on one, two, and / or three sides of one or more electrode and fiber pad assemblies.

[0052] In a further selected embodiment of the exemplary preferred embodiment, the lead-acid battery is provided with an electrode array consisting of one or more negative electrodes and one or more positive electrodes arranged alternately with each other. A porous membrane encapsulation is further provided to encapsulate at least one of the one or more negative electrodes located therein. The porous membrane includes ribs on one or more surfaces, and a fiber pad is located within the encapsulation. The ribs may be at least partially on the surface of the porous membrane adjacent to the fiber pad. The ribs may have a height of about 10 μm to about 2.0 mm, about 5 μm to about 300 μm, or about 25 μm to about 200 μm. Additionally, the fiber pad may encapsulate at least one of the one or more negative electrodes. Further, the fiber pad may be at least partially integrated into the negative electrode.

[0053] As an alternative, the fiber pad can be a discrete element located between the ribs and has a thickness of about 50% to about 150% of the rib height. In selected aspects of the invention, the fiber pad can be located between the negative electrode and the porous membrane. The fiber pad can be one or more of glass fibers, pulp, polymers, and combinations thereof. The fiber pad can be formed from a polymer combined with one or more of glass fibers, pulp, and combinations thereof; wherein the polymer can be one or more of polyolefins, polyesters, polyamides, polyimides, and combinations thereof. Alternatively, the fiber pad can be an inorganic material, such as silica. The fiber pad can be a spunbond melt nonwoven composite material or a carbon fiber nonwoven material.

[0054] In addition, the fiber mat may additionally contain a carbon component, either as part of the mat or in a layer adjacent to the negative electrode. For example, the fiber mat may contain carbon fibers, conductive carbon, graphite, artificial graphite, activated carbon, carbon paper, acetylene black, carbon black, high surface area carbon black, graphene, high surface area graphene, Keitjen black, carbon fibers, carbon filaments, carbon nanotubes, open-cell carbon foam, carbon mats, carbon felt, carbon buckyminster fullerenes (Bucky Balls), aqueous carbon suspensions, flake graphite, carbon oxide, and combinations thereof. Furthermore, the fiber mat may contain nucleating additives, such as carbon or barium sulfate (BaSO4) as described above.

[0055] In selected embodiments, the porous membrane may have ribs on both of its surfaces. Furthermore, the porous membrane may be one or more of natural materials, synthetic materials, polyolefins, phenolic resins, polyvinyl chloride (PVC), natural rubber, synthetic rubber, synthetic wood pulp, glass fiber, lignin, cellulose fibers, and combinations thereof. Specifically, the porous membrane may be polyethylene, silica, and processing oils.

[0056] In a selected aspect of the invention, the porous membrane can be sealed on one side, two sides, or three sides of the negative electrode. Alternatively, a fiber pad can be sealed on one side, two sides, or three sides of the negative electrode.

[0057] In a selected embodiment of the invention, a system is configured to provide a vehicle that utilizes one or more batteries as fully described herein. The vehicle may be an automobile, truck, motorcycle, all-terrain vehicle, motorbike, forklift, golf cart, hybrid vehicle, hybrid electric vehicle, electric vehicle, idle start-stop (ISS) vehicle, electric rickshaw battery, electric tricycle, electric bicycle, wheelchair, or marine vessel.

[0058] In selected embodiments, the lead-acid battery as fully described herein can be a flat battery, a flooded lead-acid battery, an enhanced flooded lead-acid battery (EFB), a valve-regulated lead-acid (VRLA) battery, a gel battery, an absorbent glass mat (AGM) battery, a deep-cycle battery, a tubular battery, an inverter battery, a vehicle battery, a start-light-ignition (SLI) vehicle battery, an idle-start-stop (ISS) vehicle battery, an automobile battery, a truck battery, a motorcycle battery, an all-terrain vehicle battery, a forklift battery, a golf cart battery, a hybrid electric vehicle battery, an electric vehicle battery, a wheelchair battery, an electric rickshaw battery, an electric tricycle battery, an electric bicycle battery, or a marine vessel battery.

[0059] In selected embodiments, a method is provided for preventing or mitigating acid displacement in lead-acid batteries, flooded lead-acid batteries, or flooded lead-acid batteries operating in or to be operated in a partially charged state. This method may include manufacturing a battery having a structure substantially the same as any battery described herein.

[0060] New or improved systems, vehicles, batteries, enhanced flooded lead-acid batteries, deep-cycle batteries, separators, battery separators, enhanced flooded lead-acid battery separators, deep-cycle battery separators, separators, fiber pads, battery cells, electrodes, and / or methods of manufacturing and / or using such batteries, enhanced flooded lead-acid batteries, deep-cycle batteries, separators, battery separators, enhanced flooded lead-acid battery separators, deep-cycle battery separators, fiber pads, battery cells, and / or electrodes as described or demonstrated herein.

[0061] New or improved batteries, particularly lead-acid batteries as shown and / or described herein; new or improved systems, vehicles, batteries, enhanced flooded lead-acid batteries, deep-cycle batteries, separators, battery separators, enhanced flooded lead-acid battery separators, deep-cycle battery separators, separators, fiber pads, battery cells, electrodes, and / or methods of manufacturing and / or using such systems, vehicles, batteries, enhanced flooded lead-acid batteries, deep-cycle batteries, separators, battery separators, enhanced flooded lead-acid battery separators, deep-cycle battery separators, separators, fiber pads, battery cells, and / or electrodes; improved batteries having improved separators for lead-acid batteries, and / or improved methods of using such batteries having such improved separators; methods, systems, processes, and battery separators used to extend battery life, reduce battery failure, reduce water consumption, reduce float charge current, reduce increase in internal resistance, improve wettability, reduce acid stratification, improve acid diffusion, and retain active materials in lead-acid batteries. The following are considered as improvements in battery technology: a battery for reducing active material shedding and / or improving uniformity; an improved separator for a lead-acid battery, wherein the separator includes an improved functional coating; an improved battery separator for reducing acid stratification; an improved battery separator for improving acid diffusion; an improved lead-acid battery for retaining active material; an improved lead-acid battery separator for reducing active material shedding; an improved lead-acid battery including such improved separators; a long-life automotive lead-acid battery; an improved flooded lead-acid battery; and / or the like; and / or batteries having reduced acid stratification, improved acid diffusion, improved active material retention capacity, and / or increased ability to reduce active material shedding; a battery having a polyethylene separator and a negative electrode with a fiber pad disposed therebetween; and / or a method of manufacturing and / or using such a battery; a battery having a porous membrane and a fiber pad laminated thereon, wherein in such a battery the fiber pad is adjacent to the negative electrode; and / or a method of manufacturing and / or using such a battery.

[0062] As described herein, the exemplary separator can be used in lead-acid batteries for a variety of applications. Such applications may include, for example: partial state-of-charge applications; deep cycle applications; automotive applications; truck applications; motorcycle applications; mobility-powered applications, such as forklifts, golf carts, etc.; electric vehicle applications; hybrid electric vehicle (HEV) applications; ISS vehicle applications; rickshaw applications; electric tricycle applications; electric bicycle applications; marine applications; and energy harvesting and storage applications, such as renewable and / or alternative energy harvesting and storage, such as wind and solar power. Furthermore, the exemplary separator can be used in a variety of batteries. Such exemplary batteries may include, for example: flooded lead-acid batteries, such as enhanced flooded lead-acid batteries; AGM batteries; VRLA batteries; flat batteries; tubular batteries; partially charged batteries; deep-cycle batteries; automotive batteries; truck batteries; motorcycle batteries; mobile power batteries, such as forklift batteries, golf cart batteries, etc.; electric vehicle batteries; hybrid electric vehicle (HEV) batteries; ISS vehicle batteries; electric rickshaw batteries; electric tricycle batteries; electric bicycle batteries; marine batteries; energy harvesting and storage batteries, such as renewable and / or alternative energy harvesting and storage, such as wind power, solar power, etc. Attached Figure Description

[0063] Figure 1 A typical flooded lead-acid battery is illustrated schematically.

[0064] Figure 2A and 2B This is a side view illustration of an electrode / septum array embodiment according to an exemplary embodiment of this specification.

[0065] Figure 3A and 3B This is a side view description of an electrode / septum array embodiment according to an exemplary embodiment of this specification.

[0066] Figure 4 This is a side view of an embodiment of an electrode / septum array according to an exemplary embodiment of this specification.

[0067] Figure 5A and 5B This is a side view illustration of an electrode / septum array embodiment according to an exemplary embodiment of this specification.

[0068] Figure 6A and 6B This is a side view illustration of an electrode / septum array embodiment according to an exemplary embodiment of this specification.

[0069] Figure 7A and 7BThis is a photograph of an exemplary fiber mat as described in this disclosure.

[0070] Figure 8A and 8B yes Figure 7A and 7B A higher resolution photograph of an exemplary fiber mat, Figure 8A It is a top view. Figure 8B Take the photo at an angle to the plane of the mat.

[0071] Figure 9 The image shown is a low-magnification SEM image comparing the exemplary fiber pad described herein with a conventional glass pad.

[0072] Figure 10 It shows a ratio Figure 11 SEM images with higher magnification Figure 11 This is a SEM image of an exemplary fiber mat as described in this disclosure.

[0073] Figure 11 The image is an SEM image of an exemplary fiber pad as described in this disclosure, highlighting the fiber diameter.

[0074] Figure 12 The image is an SEM image of an exemplary fiber pad as described in this disclosure, highlighting the pore area.

[0075] Figure 13A and 13B The diagram shows longitudinal ribs in the machining direction and transverse or cross-cut ribs across the machining direction.

[0076] Figures 14A to 15B This is a side view of an exemplary porous membrane, detailing the membrane dimensions of the positive and negative electrode fins. Detailed Implementation

[0077] The embodiments described herein can be more readily and best understood by referring to the following detailed description, examples, and accompanying drawings. Furthermore, various batteries, vehicles, or devices and methods for preventing acid stratification, among other things, are described herein; however, this is not limited to the specific embodiments presented in the detailed description, examples, and drawings. It should be recognized that these embodiments are merely illustrative of the principles of the invention. Many modifications and changes will be apparent to those skilled in the art without departing from the disclosed subject matter.

[0078] lead-acid batteries For reference Figure 1An exemplary lead-acid battery 50 (e.g., EFB) is provided with an array 50a of alternating positive electrodes 52 and negative electrodes 54, such that the positive electrodes 52 are interspersed between the negative electrodes 54. The array 50a is also provided with a separator assembly 100 interspersed between each electrode 52, 54, thereby separating the electrodes 52, 54 to prevent contact between the electrodes 52, 54. The array 50a is substantially immersed in a sulfuric acid (H2SO4) electrolyte 56 (e.g., sulfuric acid having an exemplary specific gravity between about 1.20 and 1.35 relative to water). The positive electrode 52 is electrically connected to the positive terminal 51, and the negative electrode 54 is electrically connected to the negative terminal 53. The separator assembly 100 includes a porous membrane ( Figure 2A -8 of 200), and may additionally include one or more fiber pads (one or more) Figure 2A -300 in 8).

[0079] There are no particular limitations on the lead-acid batteries described herein, and they can be flooded lead-acid batteries, such as enhanced flooded lead-acid batteries, absorbent glass mat (AGM) batteries, valve-regulated lead-acid (VRLA) batteries, gel batteries, and / or the like. In some preferred embodiments, the lead-acid batteries described herein are flooded lead-acid batteries, at least because some of the content disclosed herein is dedicated to addressing the problems of flooded lead-acid batteries (especially flooded lead-acid batteries operating in a partially charged state or in a partially charged state), namely acid stratification and active material shedding.

[0080] As described herein, the exemplary separator can be used in lead-acid batteries for a variety of applications. Such applications may include, for example: partial state-of-charge applications; deep cycle applications; automotive applications; truck applications; motorcycle applications; mobility-powered applications, such as forklifts, golf carts, etc.; electric vehicle applications; hybrid electric vehicle (HEV) applications; ISS vehicle applications; electric rickshaw applications; electric tricycle applications; electric bicycle applications; marine applications; and energy harvesting and storage applications, such as renewable and / or alternative energy harvesting and storage, such as wind power, solar power, etc. Furthermore, the exemplary separator can be used in a variety of batteries. Such exemplary batteries may include, for example: flooded lead-acid batteries, such as enhanced flooded lead-acid batteries; AGM batteries; VRLA batteries; flat battery; tubular battery; partially charged battery; deep cycle battery; automotive battery; truck battery; motorcycle battery; mobile power battery, such as forklift battery, golf cart battery, etc.; electric vehicle battery; hybrid electric vehicle (HEV) battery; ISS vehicle battery; electric rickshaw battery; electric tricycle battery; electric bicycle battery; marine battery; energy harvesting and storage battery, such as renewable and / or alternative energy harvesting and storage, such as wind power, solar power, etc.

[0081] Negative and positive electrodes There are no particular limitations on the positive electrode (or positive electrode plate) and negative electrode (or negative electrode plate) disclosed herein, and they can be any acceptable positive or negative electrode known to be usable in lead-acid batteries. Typically, in lead-acid batteries, the negative electrode or negative electrode plate is configured with a lead oxide (PbO2) grid and coated with a negative electrode active material (NAM); the positive electrode or positive electrode plate is configured with a sponge lead (Pb) grid and coated with a positive electrode active material (PAM). When used herein, the terms "electrode" and "plate" are used interchangeably. In some preferred embodiments, the electrode may have a planteplate configuration, a flat plate configuration, or a tubular electrode configuration.

[0082] An exemplary electrode with a planar structure is provided with a grid and an active material [e.g., a positive active material (PAM) or a negative active material (NAM)]. The grid may be made solely of lead or of a lead alloy having at least one of antimony, calcium, tin, selenium, or combinations thereof. The amount of additive added to lead may be, for example, about 1% to about 20%, about 1% to about 15%, about 1% to about 10%, about 1% to about 6%, about 1% to about 5%, about 1% to about 4%, about 1% to about 3%, about 1% to about 2%, and so on. In certain selected embodiments, the grid may be made of an alloy of lead and antimony. Antimony is believed to improve hardness. In other selected embodiments, the grid may be made of an alloy of lead and calcium. Calcium is believed to improve hardness. In some selected embodiments, tin may be added to the alloy of lead and calcium or the alloy of lead and antimony to improve cycle life. The active material in the electrode with the planar structure is formed by applying a paste to the grid. The paste can be prepared as a mixture of lead (e.g., lead oxide), water, and sulfuric acid. In some embodiments, the electrode can be cured after the paste is applied.

[0083] An exemplary electrode with a tubular structure is provided with a series of spikes extending downward from the top rod; this is referred to as a grate. The grate can be made solely of lead or of lead and at least one selected from antimony, calcium, tin, and selenium. The amount of additive added to lead can be 1% to 20%, 1% to 15%, 1% to 10%, 1% to 6%, 1% to 5%, 1% to 4%, 1% to 3%, 1% to 2%, etc. In some preferred embodiments, the grate or grid can be made of lead and antimony. Antimony is believed to improve hardness. In some other embodiments, which may be preferred, the grid (grate) is made of lead and calcium. Calcium is believed to improve hardness. In some embodiments, tin can be added to lead and calcium or an alloy of lead and antimony to improve cycle performance. Parallel tubes or collars surround the spikes and retain the active material (positive or negative electrode active material). These collars can be made of porous inert fabric or nonwoven fabric.

[0084] Electrode array For reference Figure 2A and 2B As generally described above, the exemplary electrode / separator array 50a is provided with an array of positive electrodes 52 and an array of negative electrodes 54 interspersed therebetween, and an array of separator assembly 100 is interspersed between each electrode 52, 54. As shown, the separator assembly 100 is provided with a porous membrane 200 (which may or may not have positive electrode ribs). Figure 2A (or not shown in 2B, but described below) and / or negative electrode rib [ Figure 2A (or not shown in 2B, but described below) and fiber pad 300. Alternatively, fiber pad 300 can be one or more pads. Figure 2A As shown, the fiber pad 300 is arranged adjacent to one or more positive electrodes 52 and the porous membrane 200; the porous membrane 200 is arranged adjacent to one or more negative electrodes 54 and the fiber pad 300. Figure 2B As shown, the fiber pad 300 is arranged adjacent to and in close contact with one or more negative electrodes 54 and the porous membrane 200; the porous membrane 200 is arranged adjacent to one or more positive electrodes 52 and the fiber pad 300. The separator assembly 100 may be provided with the porous membrane 200 and the fiber pad 300, which are attached to each other by adhesives, thermosetting, ultrasonic welding or sealing, ultrasonic stitching, co-extrusion, and / or combinations thereof. Alternatively, the separator assembly 100 may be provided with the porous membrane 200 and the fiber pad 300 not attached to each other. As shown, the separator assembly 100 is configured as a hinged structure. Alternatively, the separator assembly 100 may be configured as a sleeve, a hybrid sleeve, a bag, a sleeve, a wrapper, a fold, or a combination thereof. Combination refers to the possibility of using different configurations throughout the electrode / separator array 50a.

[0085] For reference Figure 3A and 3B As generally described above, the exemplary electrode / separator array 50a is provided with an array of positive electrodes 52 and an array of negative electrodes 54 interspersed therebetween, and an array of separator assemblies 100 is interspersed between each electrode 52, 54. As shown, the separator assembly 100 is provided with a porous membrane 200 (which may or may not have positive electrode ribs (for clarity)). Figure 3A (or not shown in 3B, but described below) and / or negative electrode rib [for clarity, Figure 3A (or not shown in 3B, but described below) and fiber pad 300. Alternatively, fiber pad 300 can be one or more pads. Figure 3A As shown, a fiber pad 300 is arranged in an encapsulating form around one or more positive electrodes 52; a porous membrane 200 is arranged in an encapsulating form around the fiber pad 300. Figure 3BAs shown, a fiber pad 300 is arranged in a sheath form around and in close contact with one or more negative electrodes 54; a porous membrane 200 is arranged in a sheath form around the fiber pad 300. The separator assembly 100 may be provided with a porous membrane 200 and a fiber pad 300, which are attached to each other by adhesives, thermosetting, ultrasonic welding or sealing, ultrasonic stitching, co-extrusion, and / or combinations thereof. Alternatively, the separator assembly 100 may be provided with a porous membrane 200 and a fiber pad 300 that are not attached to each other. As shown, the separator assembly 100 is configured as a sheath. Alternatively, the separator assembly 100 may be configured as a hybrid sheath, bag, sleeve, wrapping, fold, or combination thereof. "Combination" refers to the possibility of using different configurations throughout the electrode / separator array 50a.

[0086] Referring now to Figure 4, as generally described above, the exemplary electrode / separator array 50a is provided with an alternating array of positive and negative electrodes 52. In Figure 4, the separator assembly 100 is provided with a porous membrane 200 (which may or may not be provided with positive electrode ribs (not shown in Figure 4, but described below) and / or negative electrode ribs [not shown in Figure 4, but described below)) and a fiber pad 300. Alternatively, the fiber pad 300 may be one or more pads. As shown, the fiber pad 300 is arranged in the form of an envelope or bag around one or more negative electrodes 52. The porous membrane 200 is arranged in the form of an envelope or bag around one or more positive electrodes 54. The porous membrane and the fiber pad may be configured as a separator envelope, which may or may not be a hybrid envelope configuration. Alternatively, the unattached porous membrane 200 and fiber pad 300 can be configured as flaps, pouches, sleeves, wrappers, folds, S-shaped wrappers, Z-shaped folds, or combinations thereof. Combinations refer to the possibility of using different configurations throughout the electrode / septum array 50a.

[0087] Now for reference Figure 5A and 5B An exemplary implementation is provided, wherein one or more fiber pads 300 are at least partially integrated into the negative electrode 54 active material of the array 50a. Figure 5A In this structure, the porous membrane 200 is arranged in an encapsulation form around the integrated assembly of the negative electrode 54 and the fiber pad 300. Figure 5B In this arrangement, a porous membrane is arranged in a sheath around the positive electrode 52. The porous membrane 200 can be configured as a sheath (as shown, it can be a hybrid sheath), flap, bag, sleeve, wrapping, and / or a combination thereof. Combination refers to the possibility of using different configurations throughout the electrode / separator array 50a. The porous membrane 200 may or may not have positive electrode ribs (for clarity, in...). Figure 5A(or not shown in 5B, but described below) and / or negative electrode rib (for clarity, in Figure 5A (or not shown in 5B, but will be described below).

[0088] As described above, the fiber pad 300 is at least partially integrated with the negative electrode active material. Therefore, the fiber pad is not merely in contact with the negative electrode surface, but is integrally attached to the negative electrode. The negative electrode active material enters the gaps and pores of the fiber pad, thereby forming a layer 350, which is a mixture of the fiber pad 300 and the negative electrode active material (NAM) of the negative electrode 54. In some embodiments, the fiber pad is integrated into the NAM at a rate of 2% to 50%. This means that 2% to 50% of the fiber pad thickness is embedded in the NAM, thereby forming a composite layer 350, which is a mixture of the fiber pad 300 and NAM. In some embodiments, the fiber pad 300 is integrated into the negative electrode 54 at a rate of 5% to 25%. In some embodiments, the fiber pad 300 is integrated into the negative electrode 54 at a rate of 5% to 20%. In some embodiments, the fiber pad 300 is integrated into the negative electrode 54 at a rate of 10% to 15%.

[0089] For reference Figure 6A and 6B As generally described above, the exemplary electrode / separator array 50a is provided with an array of positive electrodes 52 and an array of negative electrodes 54 interspersed therebetween, and an array of separator assembly 100 is interspersed between each electrode 52, 54. In FIG. 6, separator assembly 100 is provided with a porous membrane 200 (which may or may not be provided with positive electrode ribs (not shown in FIG. 6 for clarity, but described below) and / or negative electrode ribs [not shown in FIG. 6 for clarity, but described below)) and a fiber pad 300. As shown, the fiber pad 300 is arranged adjacent to one or more positive electrodes 52 and the porous membrane 200, while the porous membrane 200 is arranged adjacent to one or more negative electrodes 54 and the fiber pad 300. Separator assembly 100 may be provided with porous membrane 200 and fiber pad 300, which are attached to each other by adhesives, thermosetting, ultrasonic welding or sealing, ultrasonic stitching, co-extrusion and / or combinations thereof. As an alternative, the partition assembly 100 may be provided with a porous membrane 200 and a fiber pad 300 that are not attached to each other. For example... Figure 6A and 6B As shown, an exemplary separator assembly 100 may be provided with a porous membrane 200 having negative electrode ribs 206 arranged in the processing direction of the porous membrane 200 (i.e., longitudinally arranged from the top to the bottom of the battery). As Figure 6A As shown, strips of the exemplary fiber mat 300 are arranged between these negative electrode ribs 206. The strips of the fiber mat 300 may have a thickness of approximately 50% to approximately 150% of the height of the ribs 206. Figure 6BAs shown, an exemplary porous pad 300 is disposed between the porous membrane 200 and the negative electrode 54.

[0090] It is important to understand that, regardless of whether the active material is NAM or PAM, the fiber pad will prevent or slow down the process of the active material detaching from or separating from the electrode adjacent to the pad.

[0091] Fiber mat Preferred fiber pad compositions may be, for example, glass fibers, synthetic fibers, or any combination thereof. An exemplary embodiment of the fiber pad may be 5% to 25% synthetic fibers, with the remaining components being glass and / or adhesives. However, the pad may be entirely glass or entirely synthetic. Such examples of synthetic fibers may be polyolefins, polyethylene, polypropylene, polyester, polyethylene terephthalate (PET), polyamide, polyimide, acrylic, other plastics, pulp, and combinations thereof. Further, the fiber composition may be a polymer, homopolymer, or copolymer, or a mixture of fibers having these components. Regardless of the composition of the fiber pad, it is preferred that it be resistant to the acidic electrolyte of a lead-acid battery. These materials tend to be hydrophobic, resulting in gas trapping. Therefore, a surfactant coating as generally described herein may be added.

[0092] The fiber mat may further have a filler, such as granular silica, to increase surface area and reduce pore size. Other exemplary fillers may include silica, talc (Mg2SiO4), alumina, hydrated alumina, titanium dioxide, zirconium oxide, sodium silicate, and / or combinations thereof. Such fillers and silica may also be used in porous membranes, and are further described herein. The fiber mat composition may further have soluble fibers. The fiber mat may also include a gelling agent to help resist acid stratification. Additionally, the fiber mat may include wetting agent additives or coatings as generally described below. Exemplary fiber mats may further be provided with at least one type of carbon, such as graphite, acetylene black, graphene, and / or the like.

[0093] Exemplary fiber mats can be made of randomly placed fibers, ropes, filaments, or threads, held together by mechanical fastening, by fiber fusion, and / or by bonding the fibers with an adhesive such as a bonding medium. The formation of the web can be accomplished through a variety of processes, including dry laying, wet laying, wet felting, needle-punching felting, felting treatment, or extruding filaments onto a moving belt. In the extrusion category, two processes include spunbond (e.g., for manufacturing spunbond nonwovens) and meltblown (e.g., for manufacturing meltblown nonwovens). See *Nonwovens: Theory, Processes, Properties, and Testing* [Turbak, A., ed., Tappi Press, Atlanta, Georgia (1993)]. Chapter 8 is incorporated herein by reference. Spunbond nonwovens are formed from filaments that are first extruded, stretched, and then laid on a continuous belt. Meltblown nonwoven fabrics are formed by extruding molten polymer through a die, thinning the extruded filaments with air or steam, and then gathering them onto a moving belt. Nonwoven materials can also be meltblown spunbond materials, having one or more meltblown layers and one or more spunbond layers arranged in any order. For example, one spunbond layer and one meltblown layer, or two or more layers, arranged in any order.

[0094] There are no particular limitations on the fiber mats described herein. It can be a nonwoven material, mesh, fleece, felt, base fabric, adhesive paper, or a combination thereof. For example, a fiber mat can be a composite material consisting of adjacent nonwoven and mesh materials, multiple adjacent different nonwoven mats, multiple adjacent sheets of the same nonwoven material, or various other combinations thereof. The composite material can have one, two, or more (3 or more) sheets or layers of material that are adjacent to or may be attached to each other.

[0095] For reference Figure 7A and 7B The image shows a photograph of an exemplary embodiment of the fiber mat. Figure 8A and 8B These are high-resolution photographs of exemplary embodiments of the fiber mat. The fiber mat can be nonwoven, fleece, felt, mesh, or any combination of layers thereof. The fiber mat can be a single layer, two layers, or other multi-layer mat. Exemplary nonwoven mats can have a thickness ranging from about 100 μm to about 900 μm, and preferably from about 200 μm to about 450 μm. Figure 8A and 8B The pattern of bundled fibers is shown. This can be done during the mat formation process, where the fibers can converge at specific low points on the discharge web as the fiber flow is discharged. Alternatively, the mat can have combed fibers.

[0096] Exemplary fibers, filaments, or cords used in nonwoven fabrics may have a fiber thickness or diameter of about 7.2 μm (±0.5 μm), with a confidence limit of ±95%. Table 1 below compares the fiber diameter in μm of the nonwoven material according to the present invention and conventional glass pads.

[0097]

[0098] An exemplary nonwoven material may have approximately 1500 l / m 2 •s to approximately 2500 l / m 2 ∙s is the preferred air permeability.

[0099] Exemplary nonwoven materials may have a pore size preferably less than about 4.0 μm to 5.0 μm (effective diameter as measured by SEM). The pore size of the fiber pad is preferably smaller than the particle size of the active material used on the associated negative or positive electrode. Table 2 below compares the pore area of ​​an exemplary fiber pad according to the invention and a conventional glass pad.

[0100]

[0101] An exemplary fiber mat may have an Ω·cm ratio of approximately 6 mΩ·cm. 2 Up to approximately 14 mΩ·cm 2 The preferred resistance (ER) is within the specified range, and preferably less than 14 mΩ·cm. 2 or less than 13 mΩ·cm 2 or less than 12 mΩ·cm 2 or less than 11 mΩ·cm 2 .

[0102] An exemplary fiber mat may have a density of approximately 50 g / m². 2 Approximately 100 g / m 2 The preferred areaweight or basis weight within the range, in some embodiments, is approximately 60 g / m³. 2 Approximately 80 g / m 2 .

[0103] An exemplary fiber mat may have a preferred adhesive content in the range of about 15% to about 21%.

[0104] Exemplary fiber mats may have a preferred thickness in the range of about 200 μm to about 450 μm, and in a particular embodiment, about 350 μm to about 450 μm.

[0105] An exemplary fiber mat may have a preferred tensile strength of about 200 N / 50 mm in the machining direction (MD) and a preferred tensile strength of about 150 N / 50 mm across the machining direction (CMD).

[0106] Furthermore, the fibers of the fiber mat can be solid or hollow, and the cross-sectional shape of the fibers can be circular, round, oval, elliptical, kidney-shaped, dog-bone-shaped, racetrack-shaped, polygonal, or any combination thereof. Additionally, the exemplary fiber can have multiple components, which can be arranged side-by-side, in a core-shell configuration, or in an island configuration. Moreover, the core-shell configuration can take any of the shapes described above, and the core can be centrally located or off-center.

[0107] The fiber pad can be arranged in sheet form or in the form of a wrap, bag, sleeve, sheath, or combination thereof throughout the electrode / sealant array. An exemplary fiber pad can encapsulate the negative electrode (negative electrode encapsulation pad) such that the separator has two inner surfaces facing the negative electrode and two opposite surfaces facing the adjacent positive electrode and / or one or more porous membranes. Alternatively, another exemplary fiber pad can encapsulate the positive electrode [positive electrode encapsulation separator (pad)] such that the fiber pad has two inner surfaces facing the positive electrode and two opposite surfaces facing the adjacent positive (negative) electrode and / or one or more porous membranes. In such an encapsulation pad, the bottom edge can be a folded or sealed crease edge surrounding the bottom of the encapsulated electrode. Further, the side edges can be open, continuously sealed seam edges or intermittently sealed seam edges. These edges can be bonded or sealed by adhesives, heating, ultrasonic welding, and / or such methods or any combination thereof.

[0108] Specific exemplary fiber pads of the partition assembly can be processed into a hybrid envelope. The hybrid envelope can be configured by forming one or more slits or openings before, during, or after the envelope is formed. The length of the opening or slit can be at least 1 / 50, 1 / 25, 1 / 20, 1 / 15, 1 / 10, 1 / 8, 1 / 5, 1 / 4, or 1 / 3 of the entire side length. The length of the opening can be 1 / 50 to 1 / 3, 1 / 25 to 1 / 3, 1 / 20 to 1 / 3, 1 / 20 to 1 / 4, 1 / 15 to 1 / 4, 1 / 15 to 1 / 5, or 1 / 10 to 1 / 5 of the entire side length. The hybrid envelope can have at least 1-5 or more openings, 1-4, 2-4, 2-3, or 2 openings, which can be evenly or unevenly distributed along the bottom edge length. Preferably, there are no openings at the corners of the envelope.

[0109] Other exemplary embodiments of the separator assembly configuration include: negative or positive electrode sheaths, negative or positive electrode sleeves, mixed negative or positive electrode sheaths, both electrodes being encapsulated or sleeved, and any combination thereof.

[0110] Sealing can be achieved by at least one of the following methods: adhesive, heat (melt) sealing, mechanical sealing, ultrasonic sealing, compression, welding, or a combination thereof. Mechanical seals can use pressure rollers with or without teeth. Mechanical seals can be performed with or without heating. Those skilled in the art will understand that certain sealing methods may be more suitable depending on the material of the fiber pad. For example, adhesive sealing may be more suitable for pads that are primarily glass fiber, while adhesive or heat sealing may be more suitable if the fiber pad contains a fusible polymer.

[0111] Now transferred to Figure 9 The image shows four low-magnification SEM images taken from two separate locations of an exemplary fiber mat and two separate locations of a conventional glass mat. The images show that the exemplary fiber mat has a more densely packed fiber web than the conventional glass mat. Furthermore, the fiber and opening area of ​​the exemplary fiber mat are smaller than those of the conventional glass mat.

[0112] exist Figure 10 In this process, SEM images of the samples are obtained as follows: First, two separate locations are identified, and then two separate regions are defined from each sample location. This is done to avoid any regional bias. (Compared to...) Figure 9 Images were captured at higher magnification. These images further show the fiber packing density and also reveal some fiber bundles, likely due to the adhesive used and its content. Fiber mats useful in the various embodiments described herein can comprise fiber bundles or twists, such as bundles or twists of glass fibers and / or synthetic fibers. In certain embodiments, such bundles or twists can be twisted before the fibers are bonded together. In such embodiments, twisting can be performed, and an adhesive can be applied to hold the twist in place. In such embodiments, partitions with fiber mats containing fiber bundles or twists can exhibit increased strength compared to partitions with conventional mats. Similarly, partitions with such fiber mats (where the fibers are twisted) can exhibit even more significant increases in strength than partitions with conventional mats. When such fiber mats according to the various preferred embodiments defined herein are manufactured using a wet-lay method, composite fiber bundles can be prepared, wherein such composite fiber bundles are provided with glass fibers and synthetic polymer fibers, for example only, such as polyester or PET fibers.

[0113] Alternatively, fibers can be bundled to form a fiber mat before or during mat formation. Bundles can be composed of various combed or twisted fibers with different material compositions, cross-sectional shapes, fiber diameters, and arbitrary combinations thereof. Bundles can be laid out in a patterned orientation, randomly placed, or a combination thereof. Bundled fibers can be laid on and / or within a randomly placed nonwoven material or fiber mat layer. Therefore, the resulting fiber mat can have a corrugated surface, a non-corrugated surface, or a combination thereof. Figure 8A and 8B This is a photograph of an exemplary fiber mat with a corrugated surface. Bundles can also be formed during mat production. Bundles can be formed simply by using the carrier yarn or surface profile used in mat production. Furthermore, the mat can be laid in two separate processes. For example, bundles can be formed using a water-insoluble adhesive, and then a second layer of nonwoven fibers can be laid to hold the fibers together. Bundles can be located on one or both surfaces of the mat.

[0114] Figure 11 Images are shown for measuring the fiber diameter of an exemplary fiber mat. The diameter is obtained by measuring the linear distance across a single fiber, without measuring fibers within a bundle, and two diameters are taken for each fiber being measured (if possible). (Source: [Original Source Name]) Figure 12 The data is listed in Table 1 above. Figure 12 This is an image used to measure the pore size of a fiber mat. (Source: [Original Source Name]) Figure 12 The data is listed in Table 2 above.

[0115] The fiber mat may additionally contain a carbon component, either as part of the mat or in a layer adjacent to the negative electrode. For example, the fiber mat may contain carbon fibers, conductive carbon, graphite, artificial graphite, activated carbon, carbon paper, acetylene black, carbon black, high surface area carbon black, graphene, high surface area graphene, Keitjen black, carbon fibers, carbon filaments, carbon nanotubes, open-cell carbon foam, carbon mats, carbon felt, carbon buckminster fullerene (buckyballs), aqueous carbon suspensions, sheet graphite, carbon oxide, and combinations thereof. Additionally, the fiber mat may contain nucleating additives, such as the carbon or barium sulfate (BaSO4) described above.

[0116] porous membrane Physical description There are no particular limitations on the porous membrane; it can be any porous membrane with pores of any size (e.g., macropores, micropores, nanopores, etc.) and can be made of any material. In some preferred embodiments, the porous membrane is a microporous membrane, such as a battery separator. For example, a microporous membrane can be made of any material. ® Or polyethylene battery separators manufactured now or in the future by any other lead-acid battery separator manufacturer.

[0117] In a preferred embodiment, the porous membrane is preferably a microporous membrane (having pores less than about 1 μm), mesoporous membrane, or macroporous membrane (having pores greater than about 1 μm) made of natural or synthetic materials such as polyolefins, polyethylene, polypropylene, phenolic resins, PVC, rubber, synthetic wood pulp (SWP), glass fiber, cellulose fiber, or combinations thereof. More preferably, the porous membrane is a microporous membrane made of a thermoplastic polymer. Preferred microporous membranes may have a pore size of about 0.1 μm (100 nanometers) and a porosity of about 60%. In principle, thermoplastic polymers may include all acid-resistant thermoplastic materials suitable for lead-acid batteries. Preferred thermoplastic polymers include polyethylene compounds and polyolefins. Polyethylene compounds include, for example, polyvinyl chloride (PVC). Polyolefins include, for example, polyethylene [such as ultra-high molecular weight polyethylene (UHMWPE)] and polypropylene. A preferred embodiment may include a mixture of filler (e.g., silica) and UHMWPE.

[0118] In some embodiments, the porous membrane has a pore size of less than 5 μm, preferably less than 1 μm. Preferably, more than 50% of the pores are about 0.5 μm or smaller. It may be preferred that at least 90% of the pores have a diameter of less than about 0.9 μm. The microporous separator preferably has an average pore size in the range of about 0.05 μm to about 0.9 μm, and in some cases, about 0.1 μm to about 0.3 μm.

[0119] In some cases, pore size can be measured using the mercury intrusion porosimetry method described in Ritter, HL and Drake, LC, Ind. Eng. Chem. Anal. Ed., 17, 787 (1945). According to this method, mercury is forced into pores of different sizes by varying the pressure applied to it using a porosimeter (Model 2000 porosimeter, Carlo Erba). The pore distribution can be determined by evaluating the raw data using MILESTONE 200 software.

[0120] In a particular exemplary embodiment, the porous membrane 200 is provided with a back mesh 202, which may be provided with an array 204, 206 of one or more ribs extending from one or two main surfaces. When the porous membrane 200 is placed in a typical lead-acid battery, the back mesh 202 typically has a surface 202p facing the positive electrode and a surface 202n facing the negative electrode. (Refer to...) Figures 13A to 1 5 B describes or defines an exemplary porous membrane based on a set of typical dimensions relative to its back mesh and ribs (although not all of them are required).

[0121] refer to Figure 13AAn exemplary porous membrane 200 is provided with a back mesh 202, which has a processing direction (as indicated by " "). md (Depicted by vertical arrows) and across the machining direction (marked by vertical arrows) and (marked by vertical arrows) cmd (The horizontal arrow line is used to depict this). The porous membrane 200 is also provided with a positive electrode rib array 204, which, when arranged in a lead-acid battery, extends from the surface 202p facing the positive electrode. The positive electrode ribs 204 are substantially in the processing direction. md Vertical alignment. The positive electrode rib array 204 is spaced at substantially the same interval. spacing 正极 ( Spacing Pos (Across the entire cross-processing direction) cmd The upper part is separated by a spacer. Rib 204 can be a positive electrode rib 204. (See reference...) Figure 13B An exemplary porous membrane 200 is provided with a back mesh 202, which has a processing direction (as indicated by " "). md (Depicted by vertical arrows) and across the machining direction (marked by vertical arrows) and (marked by vertical arrows) cmd (The horizontal arrow line is used to depict this). The porous membrane 200 is also provided with a negative electrode rib array 206, which, when arranged in a lead-acid battery, extends from the surface 202n facing the negative electrode. The negative electrode ribs 206 are substantially across the processing direction. cmd The upper horizontal alignment, and can be referred to as cross negative ribs 206. The negative rib array 204 (206) is spaced at substantially the same interval. spacing 负极 ( Spacing Neg In the longitudinal processing direction md The upper part is separated by a partition.

[0122] refer to Figure 14A An exemplary porous membrane 200 is provided with a back mesh 202, which has a back mesh thickness and dimensions of [missing information]. Back net ( Backweb The porous membrane 200 is also provided with a positive electrode rib array 204, which extends from the positive electrode-facing surface 202p of the porous membrane and is substantially in the processing direction. md Top alignment. Positive electrode rib 204 has: rib bottom width, dimension [missing information]. bottom width 正极 ( BaseW Pos ); Rib tip width, dimension is Tip width 正极 ( TipW Pos ); Positive electrode rib height, dimension is high 正极 ( Height Pos The distance between ribs, the dimension is... SpacingPos The porous membrane 200 is also provided with a negative electrode rib array 206, which extends from the negative electrode-facing surface 202n of the porous membrane. The negative electrode ribs 206 are substantially across the processing direction. cmd Top aligned and with negative electrode rib height, dimensions are high 负极 ( Height Neg Ultimately, the porous membrane consists of a total thickness [dimensions of...]. Total thickness ( Overall The thickness of the back mesh is defined as equal to the thickness of the back mesh. Backweb Positive rib height Height Pos and negative electrode rib height Height Neg The sum. Now refer to Figure 14B It shows the relationship with Figure 14A The exemplary porous membrane 200 shown is substantially the same as that shown, and it also has a negative electrode rib bottom width. BaseW Neg Width of negative electrode rib tip TipW Neg Spacing between negative electrode ribs Spacing Neg .

[0123] refer to Figure 15A An exemplary porous membrane 200 is provided with a back mesh 202, which has a back mesh thickness and dimensions of [missing information]. Backweb The porous membrane 200 is also provided with a positive electrode rib array 204, which extends from the positive electrode-facing surface 202p of the porous membrane and is substantially in the processing direction. md Top alignment. Positive electrode rib 204 has: rib bottom width, dimension [missing information]. BaseW Pos ; Rib tip width, dimension is TipW Pos The height of the positive electrode rib, with dimensions of [missing information]. Height Pos The distance between ribs, the dimension is Spacing Pos The porous membrane 200 is also provided with a negative electrode rib array 206, which extends from the negative electrode-facing surface 202n of the porous membrane. The negative electrode ribs 206 are substantially across the processing direction. cmd Top aligned and with negative electrode rib height, dimensions are Height Neg Ultimately, the porous membrane consists of a total thickness (dimensions of...). Overall The thickness of the back mesh is limited to the following: Backweb Positive rib height Height Pos and negative electrode rib height Height Neg The sum. Now refer to Figure 15B It shows the relationship with Figure 15A The exemplary porous membrane 200 shown is substantially the same as that shown, and it also has a negative electrode rib bottom width. BaseW Neg Width of negative electrode rib tip TipW Neg Spacing between negative electrode ribs Spacing Neg Additionally, the positive electrode rib 204 is divided into serrations 204s. The positive electrode serrations 204s have a bottom length... BaseL Pos rib tip length TipL Pos and the distance between saw teeth Pitch Pos .

[0124] In a particular selected aspect of the invention, one or two of the rib arrays are selected from the following: uninterrupted ribs, discrete discontinuous ribs, continuous ribs, discontinuous ribs, angled ribs, linear ribs, longitudinal ribs extending substantially in the processing direction of the porous membrane, transverse ribs extending substantially across the processing direction of the porous membrane, transverse ribs extending substantially across the processing direction of the porous membrane, cross ribs extending substantially across the processing direction of the porous membrane, negative electrode cross ribs (NCR), discrete toothed or toothed ribs, serrated or sawtooth-shaped ribs, stacked protrusions or stacked ribs, curved or sinusoidal ribs, arranged in an uninterrupted or discontinuous zigzag pattern, grooves, trenches, textured regions, protrusions, depressions, porous, non-porous, microribs or cross microribs, and combinations thereof. One possibly preferred embodiment of the rib or shape is a positive electrode-side serrated rib and a negative electrode-side cross rib (NCR). Another possibly preferred embodiment of the rib or shape is a positive electrode-side longitudinal rib and a negative electrode-side cross rib (NCR).

[0125] The total thickness of the porous or microporous membrane (including the back mesh thickness and rib height) is preferably greater than about 100 μm and less than or equal to about 5.0 mm. The total thickness of the separator can range from about 0.15 mm to about 2.5 mm, about 0.25 mm to about 2.25 mm, about 0.5 mm to about 2.0 mm, about 0.5 mm to about 1.5 mm, or about 0.75 mm to about 1.5 mm. In some cases, the total thickness of the separator can be about 0.8 mm or about 1.1 mm.

[0126] Exemplary porous membranes for separator assemblies can be configured as flat sheets, plates or leaves, coverings, sleeves, or encapsulated or bag-shaped separators. An exemplary encapsulated porous membrane can encapsulate the positive electrode (positive electrode encapsulating separator), thus giving the porous membrane two inner sides facing the positive electrode and two outer sides facing the adjacent negative electrode. Alternatively, another exemplary encapsulated porous membrane can encapsulate the negative electrode (negative electrode encapsulating separator), thus giving the porous membrane two inner sides facing the negative electrode and two outer sides facing the adjacent positive electrode. In such encapsulated porous membranes, the bottom edge 350 can be a folded or sealed crease edge. Furthermore, the side edges 105a, 105b can be continuously or intermittently sealed seam edges. The edges can be bonded or sealed by mechanical means, adhesives, heating, ultrasonic welding, and / or similar methods or any combination thereof.

[0127] Specific exemplary porous membranes can be processed into hybrid envelopes. Hybrid envelopes can be provided by forming one or more slits or openings before, during, or after the formation of the envelope. The length of the opening can be at least 1 / 50, 1 / 25, 1 / 20, 1 / 15, 1 / 10, 1 / 8, 1 / 5, 1 / 4, or 1 / 3 of the entire edge length. The length of the opening can be 1 / 50 to 1 / 3, 1 / 25 to 1 / 3, 1 / 20 to 1 / 3, 1 / 20 to 1 / 4, 1 / 15 to 1 / 4, 1 / 15 to 1 / 5, or 1 / 10 to 1 / 5 of the entire edge length. Hybrid envelopes can have 1-5 or more openings, 1-4, 2-4, 2-3, or 2 openings, which can be uniformly or non-uniformly distributed along the length of the bottom edge. Preferably, there are no openings at the corners of the envelope.

[0128] Other exemplary embodiments of porous membrane structures include: negative or positive electrode sheaths, negative or positive electrode sleeves, negative or positive electrode mixed sheaths, two electrodes that can be encapsulated or sheathed, and any combination thereof.

[0129] In some embodiments of the invention, the ribs have a rib height of at least about 0.005 mm, 0.01 mm, 0.025 mm, 0.05 mm, 0.075 mm, 0.1 mm, 0.2 mm, 0.3 mm, 0.4 mm, 0.5 mm, 0.6 mm, 0.7 mm, 0.8 mm, 0.9 mm, 1.0 mm, 1.1 mm, 1.2 mm, 1.3 mm, 1.4 mm, 1.5 mm, 1.6 mm, 1.7 mm, 1.8 mm, 1.9 mm, 2.0 mm, 2.1 mm, 2.2 mm, 2.3 mm, 2.4 mm, 2.5 mm, 2.6 mm, 2.7 mm, 2.8 mm, 2.9 mm, or 3.0 mm.

[0130] In some embodiments of the invention, the protrusion is a short-length rib having a rib width of at least about 0.005 mm, 0.01 mm, 0.025 mm, 0.05 mm, 0.075 mm, 0.1 mm, 0.2 mm, 0.3 mm, 0.4 mm, 0.5 mm, 0.6 mm, 0.7 mm, 0.8 mm, 0.9 mm, 1.0 mm, 1.1 mm, 1.2 mm, 1.3 mm, 1.4 mm, or 1.5 mm. The ribs may have a width between approximately 0.005-1.5 mm, 0.01-1.0 mm, 0.025-1.0 mm, 0.05-1.0 mm, 0.075-1.0 mm, 0.1-1.0 mm, 0.2-1.0 mm, 0.3-1.0 mm, 0.4-1.0 mm, 0.5-1.0 mm, 0.4-0.8 mm, or 0.4-0.6 mm.

[0131] The separator may include negative electrode longitudinal or cross ribs or micro ribs, such as negative electrode ribs, having a height of about 25 μm to about 250 μm, possibly preferably about 50 μm to about 125 μm, more preferably about 75 μm.

[0132] In certain embodiments, the protrusion may include ribs, each rib having a longitudinal axis set at an angle from 0° to less than 180° relative to the top edge of the partition. In some cases, all ribs in the partition may be set at the same angle, while in other embodiments, ribs set at different angles may be present. For example, in some embodiments, the partition may include multiple rows of ribs, wherein at least some rows have ribs at an angle θ relative to the top edge of the partition. All ribs in a single row may have the same approximate angle, although in other cases, a single row may contain ribs at different angles.

[0133] In certain implementations, the entire surface of the partition will contain ribs (e.g., multiple rows of continuous or discontinuous ribs, randomly arranged ribs, ribs arranged in a certain pattern, or discontinuous ribs offset from each other within rows), while in other implementations, specific segments of the partition surface will not contain ribs. These segments may appear along any edge of the partition (including the top, bottom, or sides), or they may appear towards the center of the partition, wherein the segments are surrounded by ribbed portions on one or more sides.

[0134] In various possible preferred embodiments, the porous or microporous membrane has a back mesh with one or more ribs on its surface, such as serrated, stacked, angled, or discontinuous ribs, or combinations thereof. Preferred ribs may be 8 μm to 1 mm high and spaced 8 μm to 20 mm apart, while the preferred back mesh thickness of the microporous polyolefin separator layer (excluding ribs or protrusions) may be about 0.05 mm to about 0.50 mm (e.g., about 0.25 mm in a particular embodiment). For example, ribs may be spaced apart by approximately 0.05 mm, 0.1 mm, 0.2 mm, 0.3 mm, 0.4 mm, 0.5 mm, 0.6 mm, 0.7 mm, 0.8 mm, 0.9 mm, 1.0 mm, 1.2 mm, 1.4 mm, 1.6 mm, 1.8 mm, 2.0 mm, 2.25 mm, 2.5 mm, 2.75 mm, 3 mm, 4 mm, 5 mm, 6 mm, 7 mm, 8 mm, 9 mm, or approximately 10 mm. In some embodiments, ribs may be patterned, for example, they may be at an angle of 0°–90° relative to each other on one side of the separator layer or on both sides of the polyolefin separator. In some embodiments, acid-mixing ribs may be front ribs, positive electrode ribs, or positive electrode side ribs. Different patterns including ribs on both sides of the separator or separator layer may include positive electrode ribs and negative electrode longitudinal or cross ribs on the second or back side of the separator, such as smaller, more closely spaced negative electrode longitudinal or cross ribs or micro ribs. In some cases, the height of such negative electrode longitudinal ribs or cross ribs can be from about 0.025 mm to about 0.1 mm, and preferably about 0.075 mm, but can be as high as 0.25 mm. Other patterns may include ribs on both sides of the separator layer, with negative electrode microribs on the second or back side of the separator (microribs extending in the same direction opposite to the transverse direction compared to the main ribs on the other side of the separator). In some cases, such negative electrode microribs can have a height of from about 0.025 mm to about 0.25 mm, preferably from about 0.050 mm to about 0.125 mm.

[0135] In a particular preferred embodiment, the ribs may be serrated. The serrations may have an average tip length of about 0.05 mm to about 1 mm. For example, the average tip length may be greater than or equal to about 0.05 mm, 0.1 mm, 0.2 mm, 0.3 mm, 0.4 mm, 0.5 mm, 0.6 mm, 0.7 mm, 0.8 mm, or about 0.9 mm; and / or less than or equal to about 1.0 mm, 0.9 mm, 0.8 mm, 0.7 mm, 0.6 mm, 0.5 mm, 0.4 mm, 0.3 mm, 0.2 mm, or about 0.1 mm.

[0136] The serrations may have an average bottom length of about 0.05 mm to about 1 mm. For example, the average bottom length may be greater than or equal to about 0.05 mm, 0.1 mm, 0.2 mm, 0.3 mm, 0.4 mm, 0.5 mm, 0.6 mm, 0.7 mm, 0.8 mm or about 0.9 mm; and / or less than or equal to about 1.0 mm, 0.9 mm, 0.8 mm, 0.7 mm, 0.6 mm, 0.5 mm, 0.4 mm, 0.3 mm, 0.2 mm or about 0.1 mm.

[0137] If serrations are present, they can have an average height of about 0.05 mm to about 4 mm. For example, the average height can be greater than or equal to about 0.05 mm, 0.1 mm, 0.2 mm, 0.3 mm, 0.4 mm, 0.5 mm, 0.6 mm, 0.7 mm, 0.8 mm, or about 0.9 mm; and / or less than or equal to about 1.0 mm, 0.9 mm, 0.8 mm, 0.7 mm, 0.6 mm, 0.5 mm, 0.4 mm, 0.3 mm, 0.2 mm, or about 0.1 mm. In embodiments where the serration height is the same as the rib height, the serrated ribs can also be referred to as protrusions. Such a range can be used for separators for industrial traction start / stop batteries (where the total thickness of the separator can typically be from about 1 mm to about 4 mm) and separators for automotive start / stop batteries (where the total thickness of the separator can be slightly smaller, for example, typically from about 0.3 mm to about 1 mm).

[0138] The serrations may have an average center distance of about 0.1 mm to about 50 mm. For example, the average center distance may be greater than or equal to about 0.2 mm, 0.3 mm, 0.4 mm, 0.5 mm, 0.6 mm, 0.7 mm, 0.8 mm, 0.9 mm, 1.0 mm, 1.25 mm or about 1.5 mm; and / or less than or equal to about 1.5 mm, 1.25 mm, 1.0 mm, 0.9 mm, 0.8 mm, 0.7 mm, 0.6 mm, 0.5 mm, 0.4 mm, 0.3 mm or about 0.2 mm.

[0139] The serrations may have an average height to bottom width ratio of about 0.1:1 to about 500:1. For example, the average height to bottom width ratio may be greater than or equal to about 0.1:1, 25:1, 50:1, 100:1, 150:1, 200:1, 250:1, 300:1, 350:1 or 450:1; and / or less than or equal to about 500:1, 450:1, 400:1, 350:1, 300:1, 250:1, 200:1, 150:1, 100:1, 50:1 or 25:1.

[0140] The serrations can have an average bottom width to tip width ratio of approximately 1000:1 to approximately 0.1:1. For example, the average bottom width to tip width ratio can be greater than or equal to approximately 0.1:1, 1:1, 2:1, 3:1, 4:1, 5:1, 6:1, 7:1, 8:1, 9:1, 10:1, 15:1, 20:1, 25:1, 50:1, 100:1, 150:1, 200:1, 250:1, 300:1, 350... :1, 450:1, 500:1, 550:1, 600:1, 650:1, 700:1, 750:1, 800:1, 850:1, 900:1, 950:1 and / or less than or equal to approximately 1000:1, 950:1, 900:1, 850:1, 800:1, 750:1, 700:1, 650:1, 600:1, 550:1, 500:1, 450:1, 400:1, 350:1, 300:1, 250:1, 200:1, 150:1, 100:1, 50:1, 25:1, 20:1, 15:1, 10: 1, 9:1, 8:1, 7:1, 6:1, 5:1, 4:1, 3:1, 2:1 or 1:1.

[0141] In some embodiments, the partition may be recessed. A recess is typically a protruding feature or small patch on one or more surfaces of the partition. The thickness of the recess can be 1-99% of the partition thickness. For example, the average thickness of the recess can be less than about 95%, 90%, 85%, 80%, 75%, 70%, 65%, 60%, 55%, 50%, 45%, 40%, 35%, 30%, 25%, 20%, 15%, 10%, or 5% of the partition thickness. Recesses may be arranged in rows along the partition. Rows or lines may be spaced about 1 μm to about 10 mm apart. For example, rows can be spaced apart by approximately 0.05 mm, 0.1 mm, 0.2 mm, 0.3 mm, 0.4 mm, 0.5 mm, 0.6 mm, 0.7 mm, 0.8 mm, 0.9 mm, 1.0 mm, 1.2 mm, 1.4 mm, 1.6 mm, 1.8 mm, 2.0 mm, 2.25 mm, 2.5 mm, 2.75 mm, 3 mm, 4 mm, 5 mm, 6 mm, 7 mm, 8 mm, 9 mm, or 10 mm. Conversely, recesses can also be arranged in a random array or in a random manner.

[0142] The dent can have an average dent length of about 0.05 mm to about 1 mm. For example, the average dent length can be greater than or equal to about 0.05 mm, 0.1 mm, 0.2 mm, 0.3 mm, 0.4 mm, 0.5 mm, 0.6 mm, 0.7 mm, 0.8 mm or 0.9 mm; and / or less than or equal to about 1.0 mm, 0.9 mm, 0.8 mm, 0.7 mm, 0.6 mm, 0.5 mm, 0.4 mm, 0.3 mm, 0.2 mm or 0.1 mm.

[0143] The depression may have an average depression width of about 0.01 mm to about 1.0 mm. For example, the average depression width may be greater than or equal to about 0.05 mm, 0.1 mm, 0.2 mm, 0.3 mm, 0.4 mm, 0.5 mm, 0.6 mm, 0.7 mm, 0.8 mm or 0.9 mm; and / or less than or equal to about 1.0 mm, 0.9 mm, 0.8 mm, 0.7 mm, 0.6 mm, 0.5 mm, 0.4 mm, 0.3 mm, 0.2 mm or 0.1 mm.

[0144] The depression may have an average center distance of about 0.10 mm to about 50 mm. For example, the average center distance may be greater than or equal to about 0.2 mm, 0.3 mm, 0.4 mm, 0.5 mm, 0.6 mm, 0.7 mm, 0.8 mm, 0.9 mm, 1.0 mm, 1.25 mm or 1.5 mm; and / or less than or equal to about 1.5 mm, 1.25 mm, 1.0 mm, 0.9 mm, 0.8 mm, 0.7 mm, 0.6 mm, 0.5 mm, 0.4 mm, 0.3 mm or 0.2 mm.

[0145] The shape of the recess can be quadrilateral, such as squares and rectangles. The recess can have an average length-to-width ratio of approximately 0.1:1 to approximately 100:1. For example, the ratio of average length to bottom width can be greater than or equal to approximately 0.1:1, 1:1, 2:1, 3:1, 4:1, 5:1, 6:1, 7:1, 8:1, 9:1, 10:1, 15:1, 20:1, 25:1, 50:1, 100:1, 150:1, 200:1, 250:1, 300:1, 350:1, etc. 1. 450:1, 500:1, 550:1, 600:1, 650:1, 700:1, 750:1, 800:1, 850:1, 900:1, 950:1 and / or less than or equal to approximately 1000:1, 950:1, 900:1, 850:1, 800:1, 750:1, 700:1, 650:1, 600:1, 550:1, 500:1, 450 :1, 400:1, 350:1, 300:1, 250:1, 200:1, 150:1, 100:1, 50:1, 25:1, 20:1, 15:1, 10:1, 9:1, 8:1, 7:1, 6:1, 5:1, 4:1, 3:1, 2:1 or 1:1.

[0146] In some embodiments, the recess may be substantially circular. A circular recess may have a diameter of about 0.05 to about 1.0 mm. For example, the average recess diameter may be greater than or equal to about 0.05 mm, 0.1 mm, 0.2 mm, 0.3 mm, 0.4 mm, 0.5 mm, 0.6 mm, 0.7 mm, 0.8 mm, or 0.9 mm; and / or less than or equal to about 1.0 mm, 0.9 mm, 0.8 mm, 0.7 mm, 0.6 mm, 0.5 mm, 0.4 mm, 0.3 mm, 0.2 mm, or 0.1 mm.

[0147] Various other shapes of concave depressions may also be included. By way of example only, such concave depressions can be triangular, pentagonal, hexagonal, heptagonal, octagonal, oval, elliptical, and combinations thereof.

[0148] In some embodiments, the partition is characterized by ribs, serrations, recesses, or combinations thereof. For example, the partition may have a set of serrated ribs distributed downwards along the partition, and a second set of serrated ribs distributed horizontally along the partition. In other embodiments, the partition may have alternating sequences of serrated ribs, recesses, continuous, discontinuous, or discontinuous uninterrupted ribs, or combinations thereof.

[0149] Membrane composition In certain embodiments, the improved separator may include a porous membrane, which may be used alone or together with a fiber pad as a separator, particularly for lead-acid batteries, and the separator may be made of the following materials: natural or synthetic substrate, processing plasticizer, filler, one or more natural or synthetic rubbers and / or latexes (one or more rubbers and / or latexes may be cured or crosslinked, or uncured or uncrosslinked), one or more other additives and / or coatings (such as surfactants, antioxidants and / or the like), and any combination thereof.

[0150] substrate material In certain embodiments, exemplary natural or synthetic substrate materials may include: polymers, thermoplastic polymers, phenolic resins, natural or synthetic rubbers, synthetic wood pulp, lignin, glass fibers, synthetic fibers, cellulose fibers, and any combination thereof. In certain preferred embodiments, exemplary separators may be porous membranes made of thermoplastic polymers. In principle, exemplary thermoplastic polymers may include all acid-resistant thermoplastic materials suitable for use in lead-acid batteries. In certain preferred embodiments, exemplary thermoplastic polymers may include polyvinyl compounds and polyolefins. In certain embodiments, polyvinyl compounds may include, for example, polyvinyl chloride (PVC). In certain preferred embodiments, polyolefins may include, for example, polyethylene, polypropylene, ethylene-butene copolymers, and any combination thereof, but preferably polyethylene. In certain embodiments, exemplary natural or synthetic rubbers may include, for example, latex, uncured or uncrosslinked rubber, crosslinked or cured rubber, rubber chips or abrasive rubber, and combinations thereof.

[0151] Polyolefins In certain embodiments, the porous membrane layer preferably comprises a polyolefin, particularly polyethylene. Preferably, the polyethylene is high molecular weight polyethylene (HMWPE, e.g., polyethylene having a molecular weight of at least about 600,000). Even more preferably, the polyethylene is ultra-high molecular weight polyethylene (UHMWPE). Exemplary UHMWPE may have a molecular weight of at least about 1,000,000, particularly exceeding about 4,000,000, and most preferably about 5,000,000 to about 8,000,000, measured by a viscometer and calculated using the Margolie equation. Furthermore, exemplary UHMWPE may have a standard load melt index substantially zero (0), measured according to ASTM D 1238 (Condition E) using a standard load of 2,160 g. Furthermore, the exemplary UHMWPE may have a viscosity value of not less than about 600 ml / g, preferably not less than about 1,000 ml / g, more preferably not less than about 2,000 ml / g, and most preferably not less than about 3,000 ml / g, which was determined at 130°C in a solution of 0.02 g of polyolefin in 100 g of decahydronaphthalene.

[0152] rubber The novel porous membranes and / or fiber mats disclosed herein may comprise latex and / or rubber. As used herein, “rubber” will describe rubber, latex, natural rubber, synthetic rubber, uncured or uncrosslinked rubber, crosslinked or cured rubber, rubber chips or ground rubber, and / or mixtures or combinations thereof. Exemplary natural rubber may include blends of one or more polyisoprene materials, available from various suppliers. Exemplary synthetic rubbers include methyl rubber, polybutadiene, chloroprene rubber, butyl rubber, bromoprene rubber, polyurethane rubber, epichlorohydrin rubber, polysulfide rubber, chlorosulfonyl polyethylene, polynorborneol rubber, acrylate rubber, fluororubber, and silicone rubber, as well as copolymer rubbers such as styrene / butadiene rubber, acrylonitrile / butadiene rubber, ethylene / propylene rubber (EPM and EPDM), and ethylene / vinyl acetate rubber. Rubber may be crosslinked or uncrosslinked; in a particular preferred embodiment, the rubber is uncrosslinked. In a particular embodiment, the rubber may be a blend of crosslinked and uncrosslinked rubber.

[0153] plasticizer In specific embodiments of porous membranes, exemplary processing plasticizers may include processing oils, petroleum, paraffinic mineral oils, mineral oils, and any combination thereof. Typically, exemplary embodiments use the plasticizer while extruding the substrate material to form a film, sheet, or web. After the porous membrane is formed, the plasticizer is extracted, leaving a small amount of residual plasticizer, such as residual oil.

[0154] filler The partition may comprise a filler with a high structural morphology. Exemplary fillers may include: silica, dry-processed fine silica, precipitated silica, amorphous silica, highly brittle silica, alumina, talc, fish meal, fish bone meal, carbon, carbon black, etc., and combinations thereof. In a particular preferred embodiment, the filler is one or more types of silica. High structural morphology refers to increased surface area. The filler may have a high surface area, for example, greater than about 100 m². 2 / g、110 m 2 / g, 120m 2 / g、130 m 2 / g、140 m 2 / g, 150 m 2 / g、160 m 2 / g、170 m 2 / g、180 m 2 / g、190 m 2 / g、200 m 2 / g、210m 2 / g、220 m 2 / g、230 m 2 / g、240 m 2 / g or 250 m 2 / g. In some embodiments, the filler (e.g., silica) may have a density of about 100 to about 300 μm. 2 / g, approximately 125 to approximately 275m 2 / g, approximately 150 to approximately 250m 2 / g or preferably about 170 to about 220 m 2 / g surface area. Surface area can be measured using TriStar 3000. TMThe BET nitrogen surface area at multiple points is used for evaluation. High structural morphology allows the filler to absorb more oil during manufacturing. For example, fillers with high structural morphology have high levels of oil absorption, such as greater than about 150 ml / 100 g, 175 ml / 100 g, 200 ml / 100 g, 225 ml / 100 g, 250 ml / 100 g, 275 ml / 100 g, 300 ml / 100 g, 325 ml / 100 g, or 350 ml / 100 g. In some embodiments, the filler (e.g., silica) may have an oil absorption capacity of about 200 ml / 100 g to about 500 ml / 100 g, about 200 ml / 100 g to about 400 ml / 100 g, about 225 ml / 100 g to about 375 ml / 100 g, about 225 ml / 100 g to about 350 ml / 100 g, about 225 ml / 100 g to about 325 ml / 100 g, and preferably about 250 ml / 100 g to about 300 ml / 100 g. In some cases, silica filler with an oil absorption capacity of about 266 ml / 100 g is used. Such silica filler has a water content of about 5.1% and an oil absorption capacity of about 178 ml / g. 2 The BET surface area is approximately 23 μm, the average particle size is approximately 23 μm, the residue on a 230-mesh sieve is approximately 0.1%, and the bulk density is approximately 135 g / L.

[0155] When forming exemplary lead-acid battery separators of the type shown herein, silica, with its relatively high level of oil absorption and relatively high affinity for plasticizers (e.g., mineral oil), becomes desirablely dispersible in a mixture of polyolefins (e.g., polyethylene) and plasticizers. In the past, when large amounts of silica were used to manufacture such separators or membranes, some separators suffered from poor dispersibility due to silica agglomeration. In at least certain inventive separators shown and described herein, polyolefins such as polyethylene form shish-kebab structures because there are virtually no silica aggregates or agglomerates that inhibit the movement of polyolefin molecules when the molten polyolefin is cooled. All of this contributes to improved ion permeability through the resulting separator membrane, and the formation of the shish-kebab structure or morphology means the production of separators with lower overall ER while maintaining or even improving mechanical strength.

[0156] In some selected embodiments, the filler (e.g., silica) has an average particle size of not more than about 25 μm, and in some cases not more than about 22 μm, 20 μm, 18 μm, 15 μm, or 10 μm. In some cases, the average particle size of the filler particles is from about 15 μm to about 25 μm. The particle size and / or surface area of ​​the silica filler contribute to its oil absorption properties. The silica particles in the final product or separator may fall within the aforementioned sizes. However, the initial silica used as a raw material may appear in the form of one or more agglomerates and / or aggregates, and may have a size of about 200 μm or larger.

[0157] In some preferred embodiments, the silica used to manufacture the separator of the present invention has an increased number or quantity of surface silanol groups (surface hydroxyl groups) compared to silica fillers previously used to manufacture lead-acid battery separators. For example, silica fillers that can be used with the preferred embodiments specific herein may be silica fillers that have at least about 10%, at least about 15%, at least about 20%, at least about 25%, at least about 30%, or at least about 35% more silanol and / or hydroxyl surface groups compared to known silica fillers used to manufacture known polyolefin lead-acid battery separators.

[0158] The ratio of silanol groups (Si-OH) to silicon (Si) elements [i.e. (Si-OH) / Si] can be determined, for example, as follows.

[0159] 1. Freezing and crushing a polyolefin porous membrane (wherein a particular membrane of the present invention contains a specific type of oil-absorbing silica according to the present invention), and preparing it for solid-state nuclear magnetic resonance spectroscopy (…). 29 Powdered sample (Si-NMR).

[0160] 2. Processing powdered samples 29 Si-NMR was performed, and the spectra were observed, including the spectral intensities of Si directly bonded to hydroxyl groups (spectral values: Q2 and Q3) and the spectral intensities of Si directly bonded only to oxygen atoms (spectral value: Q4). The molecular structure of each NMR peak spectrum can be depicted as follows: Q2: (SiO)2-Si*-(OH)2: has two hydroxyl groups Q3: (SiO)3-Si*-(OH): has one hydroxyl group Q4: (SiO)4-Si*: All Si bonds are SiO Among them, Si* is an element that has been identified through NMR observation.

[0161] 3. Used for observation 29 The conditions for Si-NMR are as follows: Instrument: Bruker BioSpin Avance 500 Resonant frequency: 99.36 MHz Sample volume: 250 mg NMR tube: 7 mφ Observation method: DD / MAS Pulse width: 45° Repeat time: 100 sec Scan: 800 Magic horn spin: 5000 Hz Chemical shift reference: -22.43 ppm for silicone rubber.

[0162] 4. Numerically separate the spectral peaks and calculate the area ratio of each peak belonging to Q2, Q3, and Q4. Then, based on the ratios, calculate the molar ratio of hydroxyl groups (-OH) directly bonded to Si. The numerical peak separation conditions are as follows: Fitting range: -80 to -130 ppm Initial peak values: Q2 -93 ppm, Q3 -101 ppm, and Q4 -111 ppm, respectively. Initial maximum full width at half maximum (FWHM): Q2 is 400 Hz, Q3 is 350 Hz, and Q4 is 450 Hz, respectively. Gaussian function ratio: 80% initially, 70% to 100% during fitting.

[0163] 5. Calculate the peak area ratios (total 100) of Q2, Q3, and Q4 based on each fitted peak. The NMR peak area corresponds to the number of molecules in each silicate bond structure (therefore, for the Q4 NMR peak, there are 4 Si-O-Si bonds in the silicate structure; for the Q3 NMR peak, there are 3 Si-O-Si bonds and 1 Si-OH bond in the silicate structure; for the Q2 NMR peak, there are 2 Si-O-Si bonds and 2 Si-OH bonds in the silicate structure). Therefore, the number of hydroxyl (-OH) groups in Q2, Q3, and Q4 is multiplied by two (2), one (1), and zero (0), respectively. Add these three results together. The sum shows the molar ratio of hydroxyl (-OH) groups directly bonded to Si.

[0164] In certain embodiments, silicon dioxide may have the properties of passing through... 29The molecular ratio of OH to Si groups measured by Si-NMR (i.e., OH / Si) can be in the range of about 21:100 to 35:100, in some preferred embodiments about 23:100 to about 31:100, in certain preferred embodiments about 25:100 to about 29:100, and in other preferred embodiments at least about 27:100 or greater.

[0165] In some selected embodiments, the use of the aforementioned filler allows for the use of a larger proportion of processing oil in the extrusion step. Since the porous structure in the separator is formed partly by removing the oil after extrusion, a higher initial oil absorption results in higher porosity or a higher void volume. The processing oil is an integral part of the extrusion step and is a non-conductive component in the separator. Residual oil in the separator protects it from oxidation when in contact with the positive electrode. In the manufacture of conventional separators, the precise amount of oil in the processing step can be controlled. Generally, conventional separators are manufactured using approximately 50% to approximately 70% processing oil, approximately 55% to approximately 65% ​​in some embodiments, approximately 60% to approximately 65% ​​in some embodiments, and approximately 62% in some embodiments. Percentages are weight percentages relative to the weight of other base materials (e.g., polymers, fillers, etc.). It is known that reducing the oil to below approximately 59% can cause combustion due to increased friction with extruder components. However, increasing the oil amount to well above the specified amount may cause shrinkage during the drying stage, leading to dimensional instability. While previous attempts to increase oil content resulted in pore shrinkage or reduction during degreasing, the separators prepared as disclosed herein exhibit minimal shrinkage or reduction during degreasing, if any. Therefore, porosity can be increased without affecting pore size and dimensional stability, thereby reducing resistivity.

[0166] In certain selected embodiments, the use of the above-described filler can reduce the final oil concentration in the finished separator. Since oil is a non-conductor, reducing the oil content can increase the ionic conductivity of the separator and help reduce the separator's resistivity (ER). Therefore, separators with reduced final or residual oil content can have increased efficiency. In certain selected embodiments, separators are provided having a final or residual processing oil content (by weight) of less than about 20%, for example, between about 14% and about 20%, and in some particular embodiments, less than about 19%, 18%, 17%, 16%, 15%, 14%, 13%, 12%, 11%, 10%, 9%, 8%, 7%, 6%, or 5%.

[0167] The filler can further reduce the so-called hydrated spheres of electrolyte ions, enhancing their transmembrane transport, thereby further reducing the overall ER of the battery (such as an enhanced flooded battery) or system.

[0168] One or more fillers may contain various materials (e.g., polar materials, such as metals) that facilitate the flow of electrolyte and ions through the separator. When such separators are used in flooded batteries (e.g., enhanced flooded batteries), this also results in a reduction in overall resistance.

[0169] brittleness In certain selected embodiments, the filler may be alumina, talc, silica, or a combination thereof. In some embodiments, the filler may be precipitated silica, and in some embodiments, the precipitated silica is amorphous silica. In some embodiments, aggregates and / or agglomerates of silica are preferred, which allow the filler to be well dispersed throughout the separator, thereby reducing tortuosity and resistivity. In certain preferred embodiments, the filler (e.g., silica) is characterized by a high level of brittleness. Good brittleness improves the dispersibility of the filler throughout the polymer during the extrusion of the porous membrane, increases porosity, and thus improves the overall ionic conductivity through the separator.

[0170] Brittleness can be measured as the ability, tendency, or predisposition of silica particles or materials (aggregates or agglomerates) to break down into smaller and more dispersible particles, fragments, or components. New silica is more brittle than standard silica (breaking down into smaller fragments after 30 seconds and 60 seconds of sonication). For example, the new silica has a 50% volumetric particle size of 24.90 μm at 0 seconds of sonication, 5.17 μm at 30 seconds, and 0.49 μm at 60 seconds. Therefore, after 30 seconds of sonication, the size (diameter) of 50% volumetric silica particles is reduced by more than 50%, and after 60 seconds, by more than 75%. Thus, a potentially preferred definition of "high brittleness" could be a reduction in the average size (diameter) of silica particles of at least 50% after 30 seconds of sonication and a reduction in the average size (diameter) of at least 75% after 60 seconds of sonication (or during the processing of a resin-silica mixture to form a film). In at least certain embodiments, it may be preferred to use more brittle silica, and even more preferably brittle and multimodal silica, such as bimodal or trimodal silica in terms of brittleness. Standard silica is monomodal in terms of brittleness or particle size distribution, while the new silica appears more brittle and is bimodal (two peaks) after 30 seconds of sonication and trimodal (three peaks) after 60 seconds of sonication. These brittle and multimodal silica particles, one or more, can provide enhanced membrane and separator performance.

[0171] Using fillers having one or more of the above-described characteristics, separators with high final porosity can be produced. The separators disclosed herein can have final porosities greater than about 60%, 61%, 62%, 63%, 64%, 65%, 66%, 67%, 68%, 69%, or 70%. Porosity can be measured using gas adsorption. Porosity can be measured using a BS-TE-2060.

[0172] In some selected embodiments, the porous partition may have a larger proportion of larger pores while keeping the average pore size no greater than about 1 μm, 0.9 μm, 0.8 μm, 0.7 μm, 0.6 μm, 0.5 μm or 0.1 μm.

[0173] According to at least one embodiment, the separator is made by mixing polyethylene [such as ultra-high molecular weight polyethylene (UHMWPE)] with processing oil and filler, as well as any desired additives. According to at least one other embodiment, the separator is made by mixing ultra-high molecular weight polyethylene (UHMWPE) with processing oil and talc. According to at least one other embodiment, the separator is made by mixing UHMWPE with processing oil and silica (e.g., precipitated silica, such as amorphous precipitated silica). Additives can then be applied to the separator using one or more of the above techniques.

[0174] In addition to reducing resistance and increasing cold-start current, the preferred separator is designed to offer other advantages. In terms of assembly, the separator is easier to process with equipment, resulting in higher manufacturing efficiency. To prevent short circuits during high-speed assembly and subsequent use, this separator exhibits superior puncture strength and oxidation resistance compared to standard PE separators. Combined with the reduced resistance and increased cold-start current, battery manufacturers readily find that using these new separators improves and sustains the electrical performance of their batteries.

[0175] Additives / surfactants In certain embodiments, the exemplary separator may include one or more performance-enhancing additives added to the separator or porous membrane. These performance-enhancing additives may be surfactants, wetting agents, colorants, antistatic additives, antimony inhibitors, UV protectants, antioxidants, and / or similar substances, as well as any combination thereof. In certain embodiments, the added surfactant may be an ionic, cationic, anionic, or nonionic surfactant.

[0176] In the specific embodiments described herein, a reduced amount of anionic or nonionic surfactant is added to the porous membrane or separator of the present invention. Due to the lower amount of surfactant, desired characteristics may include reduced total organic carbon (TOC) and / or reduced volatile organic compounds (VOC).

[0177] Specific suitable surfactants are nonionic, while other suitable surfactants are anionic. Additives can be a single surfactant or a mixture of two or more surfactants, for example, two or more anionic surfactants, two or more nonionic surfactants, or at least one ionic surfactant and at least one nonionic surfactant. Specific suitable surfactants may have an HLB value of less than 6, preferably less than 3. Using these specific suitable surfactants with the separators of the invention described herein can produce further improved separators that, when used in lead-acid batteries, can provide reduced water consumption, reduced antimony poisoning, improved cycle life, reduced float current, lower float voltage, and / or such or any combination thereof. Suitable surfactants include surfactants such as alkyl sulfonates, alkyl aryl sulfonates, alkylphenol-ethylene oxide addition products, soaps, surfactants of alkyl naphthalene sulfonates; one or more sulfosuccinates, such as anionic sulfosuccinates, dialkyl esters of sulfosuccinates; amino compounds (primary, secondary, tertiary amines or quaternary amines); block copolymers of ethylene oxide and propylene oxide, various polyethylene oxides, and salts of mono- and dialkyl phosphates. Additives may include nonionic surfactants such as polyol fatty acid esters, polyethoxylated esters, polyethoxylated alcohols, alkyl polysaccharides such as alkyl polyglycosides and mixtures thereof, amine ethoxylates, sorbitol fatty acid ester ethoxylates, organosilicon surfactants, ethylene vinyl acetate terpolymers, ethoxylated alkyl aryl phosphates of fatty acids, and sucrose esters.

[0178] In a particular embodiment, the additive may be represented by a compound of formula (I). in: R is a linear or non-aromatic hydrocarbon group having 10 to 4200, preferably 13 to 4200, carbon atoms, which can be interrupted by oxygen atoms; R 1 =H、— Or —(CH2) k — H is preferred, where k = 1 or 2; M is an alkali metal or alkaline earth metal ion, H + or NH4 + Not all variables M are simultaneously equal to H. + ; n = 0 or 1; m = 0 or an integer from 10 to 200; and x = 1 or 2.

[0179] In compounds according to formula (I), the ratio of oxygen atoms to carbon atoms is in the range of 1:1.5 to 1:30, and m and n cannot both be 0. However, it is preferable that only one of the variables n and m is not equal to 0.

[0180] Non-aromatic hydrocarbon groups refer to free radicals that do not contain aromatic groups or that represent aromatic groups themselves. Hydrocarbon groups can be interrupted by oxygen atoms (i.e., they contain one or more ether groups).

[0181] R is preferably a straight-chain or branched aliphatic hydrocarbon group that can be interrupted by an oxygen atom. Saturated, non-crosslinked hydrocarbon groups are particularly preferred. However, as mentioned above, in certain embodiments, R may contain an aromatic ring.

[0182] By using compounds of formula (I) to produce battery separators, the separators can be effectively protected from oxidative damage.

[0183] Battery separators containing compounds according to formula (I) are preferred, wherein: R is a hydrocarbon group having 10 to 180, preferably 12 to 75, and very particularly preferably 14 to 40 carbon atoms, which can be interrupted by 1 to 60, preferably 1 to 20, and very particularly preferably 1 to 8 oxygen atoms, with the particularly preferred formula R. 2 —[(OC2H4)p(OC3H6) q ]— a hydrocarbon group, wherein: R 2 It is an alkyl group having 10 to 30 carbon atoms, preferably 12 to 25, and particularly preferably 14 to 20 carbon atoms, wherein R 2 It can be linear or nonlinear, such as containing aromatic rings; P is an integer from 0 to 30, preferably from 0 to 10, and particularly preferably from 0 to 4; and q is an integer from 0 to 30, preferably from 0 to 10, and especially preferably from 0 to 4; Compounds in which the sum of p and q is 0 to 10, especially 0 to 4, are particularly preferred; n=1; and m=0.

[0184] Formula R 2 —[(OC2H4) p (OC3H6) q — This should be understood to also include compounds in which the sequence of groups enclosed in square brackets differs from that shown. For example, according to the invention, it is suitable to use compounds in which the radicals enclosed in brackets are formed by alternating (OC2H4) and (OC3H6) groups.

[0185] It has been confirmed that R 2Additives having 10 to 20, preferably 14 to 18, straight-chain or branched alkyl groups are particularly advantageous. OC2H4 preferably represents OCH2CH2, and OC3H6 represents OCH(CH3)2 and / or OCH2CH2CH3.

[0186] As preferred additives, alcohols (p=q=0, m=0) are particularly noteworthy, with primary alcohols being especially preferred. Fatty alcohol ethoxylates (p=1 to 4, q=0), fatty alcohol propoxylates (p=0, q=1 to 4), and fatty alcohol alkoxylates (p=1 to 2, q=1 to 4), as well as ethoxylates of primary alcohols, are preferred. Fatty alcohol alkoxylates can be obtained, for example, by reacting the corresponding alcohol with ethylene oxide or propylene oxide.

[0187] It has been proven that m=0 type additives that are insoluble or sparingly soluble in water and sulfuric acid are particularly advantageous.

[0188] Also preferred are additives containing compounds according to formula (I), wherein: R is an alkane group having 20 to 4200, preferably 50 to 750, and very particularly preferably 80 to 225 carbon atoms; M is an alkali metal or alkaline earth metal ion, H + or Especially such as Li + Na + and K + alkali metal ions or H + Not all variables M are simultaneously equal to H. + ; n=0; m is an integer from 10 to 200; and x = 1 or 2.

[0189] Manufacturing of porous membranes In some embodiments, exemplary porous membranes can be manufactured by mixing the components in an extruder. For example, about 5% to about 15% by weight of a polymer (e.g., polyethylene, UHMWPE, etc.), about 10% to about 75% by weight of a filler (e.g., silica), about 10% to about 85% by weight of a processing oil, and optionally about 1% to about 50% by weight of rubber and / or latex can be mixed in an extruder. Exemplary porous membranes can be made by passing the components through a heated extruder, extruding the extrudate from the extruder through a die and into a gap formed by two heated press or calender rolls or rolls to form a continuous web. A large amount of processing oil can be extracted from the web using a solvent. The web can then be dried and cut into strips of a predetermined width, which are then wound onto rolls. Furthermore, various groove patterns can be engraved on the press or calender rolls (or embossing rolls can have raised elements) to impart ribs, grooves, textured areas, protrusions, and / or the like as fully described herein. The amounts of rubber, fillers, oils, and polymers are all balanced to suit operational requirements and desired diaphragm properties (such as resistance, basis weight, puncture resistance, flexural stiffness, oxidation resistance, porosity, physical strength, and flexural strength).

[0190] In addition to being incorporated into the components of an extruder, certain embodiments combine the rubber with the porous membrane after extrusion. For example, the rubber can be coated on one or both sides, preferably the side facing the negative electrode, with a liquid slurry containing rubber and / or latex, optionally silica, and water, and then dried to form a thin film of this material on the surface of an exemplary porous membrane. To improve the wettability of this layer, a wetting agent used in lead-acid batteries can be added to the slurry. In certain embodiments, the slurry may also contain one or more performance-enhancing additives as described herein. After drying, a porous layer and / or film is formed on the separator surface, which adheres very well to the porous membrane and, if present, only negligibly increases the resistance. After the rubber is added, it can be further compressed using a machine press or calender roll set or rollers. Other possible methods of applying the rubber and / or latex are by dip coating, roll coating, spray coating, or curtain coating, or any combination thereof, applying the rubber and / or latex slurry to one or more surfaces of the separator. These processes can occur before or after the processed oil is extracted, or before or after the partitions are cut into strips.

[0191] Further embodiments of the present invention involve depositing rubber onto a film by impregnation and drying.

[0192] Manufactured with performance-enhancing additives In certain embodiments, performance-enhancing additives or reagents (such as surfactants, wetting agents, colorants, antistatic additives, antioxidants, and / or the like, and any combination thereof) may also be mixed together with other components in an extruder. The porous membrane according to this disclosure can then be extruded into sheet or mesh shapes in substantially the same manner as described above, and produced as a finished product.

[0193] In certain embodiments, as a supplement or alternative to additions to the extruder, one or more additives may be applied to the porous membrane of the separator after the separator is made (e.g., after the extraction of a large amount of processing oil and before or after the addition of rubber). According to certain preferred embodiments, the additive or a solution of the additive (e.g., an aqueous solution) is applied to one or more surfaces of the separator. This variation is particularly suitable for applying non-thermally stable additives and additives soluble in the solvent used to extract the processing oil. Solvents particularly suitable as additives according to the invention are low molecular weight alcohols, such as methanol and ethanol, and mixtures of these alcohols with water. Application may be performed on the side of the separator facing the negative electrode, the side facing the positive electrode, or both sides. Application may also be performed simultaneously in a solvent bath during the extraction of the pore-forming agent (e.g., processing oil). In certain selected embodiments, a portion or both of the performance-enhancing additives (e.g., a surfactant coating) added to the extruder before separator manufacturing may combine with antimony in the battery system and deactivate it, and / or form compounds with it and / or cause it to fall into the battery slurry and / or prevent its deposition on the negative electrode. Surfactants or additives may also be added to electrolytes, glass pads, battery boxes, adhesive paper, adhesive pads and / or combinations thereof.

[0194] In certain exemplary embodiments, the additive (e.g., ionic surfactant, cationic surfactant, nonionic surfactant, anionic surfactant, or a combination thereof) may be at a concentration of at least about 0.5 g / m 2 1.0 g / m 2 1.5 g / m 2 2.0 g / m 2 2.5 g / m 2 3.0 g / m 2 3.5 g / m 2 4.0 g / m 2 4.5 g / m 2 5.0 g / m 2 5.5 g / m 2 6.0 g / m 2 6.5 g / m 2 7.0 g / m 2 7.5 g / m 2 8.0 g / m2 8.5 g / m 2 9.0 g / m 2 9.5 g / m 2 Or 10.0g / m 2 Or even as high as approximately 25.0 g / m 2 The surface area density (i.e., grams per separator surface area) or the level of addition is present. The additive can be listed below as having an area density or addition level present on the separator: at approximately 0.5 g / m². 2 Approximately 15 g / m 2 Approximately 0.5 g / m 2 Approximately 10 g / m 2 Approximately 1.0 g / m 2 To approximately 10.0 g / m 2 Approximately 1.5 g / m 2 To approximately 10.0 g / m 2 Approximately 2.0 g / m 2 To approximately 10.0 g / m 2 Approximately 2.5 g / m 2 To approximately 10.0 g / m 2 Approximately 3.0 g / m 2 To approximately 10.0 g / m 2 Approximately 3.5 g / m 2 To approximately 10.0 g / m 2 Approximately 4.0 g / m 2 To approximately 10.0 g / m 2 Approximately 4.5 g / m 2 To approximately 10.0 g / m 2 Approximately 5.0 g / m 2 To approximately 10.0 g / m 2 Approximately 5.5 g / m 2 To approximately 10.0 g / m 2 Approximately 6.0 g / m 2 To approximately 10.0 g / m 2 Approximately 6.5 g / m 2 To approximately 10.0 g / m 2 Approximately 7.0 g / m 2 To approximately 10.0 g / m 2 Approximately 7.5 g / m 2 To approximately 10.0 g / m 2 Approximately 4.5 g / m 2 Approximately 7.5 g / m 2 Approximately 5.0 g / m 2 Approximately 10.5 g / m 2 Approximately 5.0 g / m 2Approximately 11.0 g / m 2 Approximately 5.0 g / m 2 To approximately 12.0 g / m 2 Approximately 5.0 g / m 2 Approximately 15.0 g / m 2 Approximately 5.0 g / m 2 Approximately 16.0 g / m 2 Approximately 5.0 g / m 2 Approximately 17.0 g / m 2 Approximately 5.0 g / m 2 Approximately 18.0 g / m 2 Approximately 5.0 g / m 2 Approximately 19.0 g / m 2 Approximately 5.0 g / m 2 To approximately 20.0 g / m 2 Approximately 5.0 g / m 2 Approximately 21.0 g / m 2 Approximately 5.0 g / m 2 To approximately 22.0 g / m 2 Approximately 5.0 g / m 2 Approximately 23.0 g / m 2 Approximately 5.0 g / m 2 Approximately 24.0 g / m 2 Or 5.0 g / m 2 Approximately 25.0 g / m 2 between.

[0195] Additive application can also be performed by immersing the battery separator in an additive or additive solution (solvent bath addition) and removing the solvent if necessary (e.g., by drying). In this way, additive application can be combined, for example, with extraction, which is often used in membrane production processes. Other preferred methods include spraying the additive onto the surface, or dip-coating, roller-coating, or curtain-coating one or more additives onto the surface of the separator.

[0196] In certain embodiments described herein, a small amount of ionic, cationic, anionic, or nonionic surfactant is added to the separator of the present invention. In this case, desired features may include reduced total organic carbon and / or reduced volatile organic compounds (due to the lower amount of surfactant), resulting in the desired separator of the present invention according to this embodiment.

[0197] application The exemplary separators described herein can be used in a variety of exemplary batteries. Such batteries can be any lead-acid battery, such as flooded lead-acid batteries, enhanced flooded lead-acid batteries, flat batteries, tubular batteries, valve-regulated lead-acid (VRLA) batteries, gel batteries, absorbent glass mat (AGM) batteries, deep-cycle lead-acid batteries, and / or batteries operating in a partially charged state. Such batteries can be used in a variety of exemplary applications, such as vehicles, alternative energy harvesting and storage (e.g., those used in solar and wind energy harvesting and other renewable and / or alternative energy sources), inverters, uninterruptible power supply (UPS) equipment, and / or the like. There is no particular limitation on the exemplary vehicles described herein, but at least vehicles equipped with one or more of the separators or batteries described herein. In preferred embodiments, exemplary vehicles can be automobiles, trucks, motorcycles, all-terrain vehicles, motorbikes, forklifts, golf carts, wheelchairs, idle start-stop (ISS) vehicles, hybrid vehicles, hybrid electric vehicles, micro hybrid electric vehicles, electric vehicles, electric rickshaw batteries, electric tricycles, electric bicycles, boats, or any other motor vehicle. Exemplary batteries in which the separator of the present invention can be used may include: flat batteries, flooded lead-acid batteries, enhanced flooded lead-acid batteries (EFB), valve-regulated lead-acid (VRLA) batteries, gel batteries, absorbent glass mat (AGM) batteries, deep-cycle batteries, tubular batteries, inverter batteries, vehicle batteries, start-light-ignition (SLI) vehicle batteries, idle start-stop (ISS) vehicle batteries, automobile batteries, truck batteries, motorcycle batteries, all-terrain vehicle batteries, forklift batteries, golf cart batteries, hybrid electric vehicle batteries, electric vehicle batteries, electric rickshaw batteries, electric tricycle batteries, electric bicycle batteries, wheelchair batteries, marine batteries, etc.

[0198] In some preferred embodiments, the battery is used in devices that will operate in a partially charged state. For example, the battery is used in devices in which it will operate in a partially charged state under normal daily conditions (i.e., in its normal use condition, not due to misuse).

[0199] method There are no particular limitations on the methods described herein. These methods can be used to prevent acid displacement in lead-acid batteries, flooded lead-acid batteries, or flooded lead-acid batteries operating under normal conditions (not misuse) or in a partially charged state. These methods can also be used to arrange electrode arrays as described herein in lead-acid batteries.

[0200] Various embodiments of the invention have been described to achieve the various objectives of the invention. It should be understood that these embodiments are merely illustrative of the principles of the invention. Many modifications and variations will be apparent to those skilled in the art without departing from the spirit and scope of the invention.

[0201] in conclusion According to at least selected embodiments, this disclosure or invention is directed to separators, particularly separators for flooded lead-acid batteries, wherein the separator is capable of reducing or mitigating acid deficiency, reducing or mitigating acid stratification, reducing or mitigating dendrite growth, and has reduced resistance and / or the ability to increase cold start current. Furthermore, methods, systems, and battery separators disclosed herein are used to improve battery life, reduce or mitigate acid deficiency, reduce or mitigate acid stratification, reduce or mitigate dendrite growth, reduce the effects of oxidation, reduce water consumption, reduce internal resistance, improve wettability, improve acid diffusion, increase cold start current, improve uniformity, and any combination thereof in at least enhanced flooded lead-acid batteries. According to at least particular embodiments, this disclosure or invention is directed to improved separators for enhanced flooded lead-acid batteries, wherein the separator includes an improved and novel rib design, and improved separator elasticity. According to at least a particular embodiment, this disclosure or invention is dedicated to an improved separator for enhanced flooded lead-acid batteries, wherein the separator includes performance-enhancing additives or coatings, increased oxidation resistance, increased porosity, increased pore volume, amorphous silica, silica with higher oil absorption, silica with more silanol groups, silica with an OH to Si ratio of 21:100 to 35:100, a polyolefin microporous membrane having a shish-kebab structure or morphology, containing 40% or more of particulate filler by weight of the membrane and polymer [e.g., ultra-high molecular weight polyethylene (UHMWPE)] (having a shish-kebab configuration with extended chain crystals (shish configuration) and folded chain crystals (kebab configuration), and the average repetition period of the kebab configuration being 1 nm to 150 nm), reduced sheet thickness, reduced tortuosity, reduced thickness, reduced oil content, increased wettability, improved acid diffusion and / or the like, and any combination thereof.

[0202] According to at least a first aspect of a specific selected embodiment, a lead-acid battery separator is provided with a porous membrane having a polymer and a filler. The porous membrane is provided with at least a first surface having at least a first plurality of ribs extending from the first surface. The first plurality of ribs are provided with a first plurality of teeth or discontinuous peaks or protrusions, wherein each of the first plurality of teeth or discontinuous peaks or protrusions is close to each other to provide elasticity to the separator. Such elasticity may refer to the separator's ability to resist deflection under pressure generated by NAM swelling. Such closeness may be at least about 1.5 mm from one tooth, peak, or protrusion to another. The separator may further be provided with a continuous bottom portion having the first plurality of teeth or discontinuous peaks or protrusions extending from the bottom portion.

[0203] In a particular embodiment, the partition may have a continuous bottom portion having a first plurality of teeth or discontinuous peaks or protrusions extending from the bottom portion. The bottom portion may be wider than the width of the teeth or discontinuous peaks or protrusions. Furthermore, the bottom portion may extend continuously between each tooth or discontinuous peak or protrusion.

[0204] According to at least a specific selected embodiment, the partition may be provided with one or more of the following ribs: uninterrupted ribs, discrete discontinuous ribs, continuous ribs, discontinuous ribs, discontinuous peaks, discontinuous protrusions, angled ribs, linear ribs, longitudinal ribs extending substantially in the processing direction of the porous membrane, transverse ribs extending substantially across the processing direction of the porous membrane, transverse ribs extending substantially across the processing direction of the partition, teeth, toothed ribs, serrated protrusions, serrated ribs, stacked protrusions, stacked ribs, curved ribs, sinusoidal ribs, arranged in a continuous zigzag zigzag pattern, arranged in a discontinuous zigzag zigzag pattern, grooves, trenches, textured areas, protrusions, depressions, pillars, micropillars, porous, non-porous, microribs, intersecting microribs, and combinations thereof.

[0205] At least a portion of the first plurality of ribs may be defined by an angle that is neither parallel nor orthogonal to the edge of the partition. Further, this angle may be defined as an angle relative to the processing direction of the porous membrane, and the angle may be one of the following: greater than zero degrees (0°) and less than 180 degrees (180°), and greater than 180 degrees (180°) and less than 360 degrees (360°). In certain aspects of the disclosed embodiments, the angle may vary throughout the plurality of ribs.

[0206] In a particular selected aspect of the invention, the first plurality of ribs may have a spacing of about 1.5 mm to about 10 mm across the machining direction, and the plurality of teeth or discontinuous peaks or protrusions may have a spacing of about 1.5 mm to about 10 mm across the machining direction.

[0207] In a particular selected embodiment, the separator may be provided with a second plurality of ribs extending from the second surface of the porous membrane. The second plurality of ribs may be one or more of the following: uninterrupted ribs, discrete discontinuous ribs, continuous ribs, discontinuous ribs, discontinuous peaks, discontinuous protrusions, angled ribs, linear ribs, longitudinal ribs extending substantially in the processing direction of the porous membrane, transverse ribs extending substantially across the processing direction of the porous membrane, transverse ribs extending substantially across the processing direction of the separator, teeth, toothed ribs, stacked protrusions, stacked ribs, curved ribs, sinusoidal ribs, arranged in a continuous zigzag pattern, arranged in a discontinuous zigzag pattern, grooves, trenches, textured regions, protrusions, depressions, pillars, micropillars, porous, non-porous, microribs, intersecting microribs, and combinations thereof.

[0208] At least a portion of the second plurality of ribs may be defined by an angle that is neither parallel nor orthogonal to the edge of the partition. Further, this angle may be defined as an angle relative to the processing direction of the porous membrane, and the angle may be one of the following: between greater than zero degrees (0°) and less than 180 degrees (180°), and between greater than 180 degrees (180°) and less than 360 degrees (360°). In certain aspects of the disclosed embodiments, the angle may vary throughout the plurality of ribs.

[0209] The second plurality of ribs have a spacing of approximately 1.5 mm to approximately 10 mm across the machining direction or in the machining direction.

[0210] The first surface may be provided with one or more ribs, the height of which differs from a first plurality of ribs adjacent to the edge of the lead-acid battery separator. Similarly, the second surface may be provided with one or more ribs, the height of which differs from a second plurality of ribs adjacent to the edge of the lead-acid battery separator.

[0211] In selected embodiments, the polymer may be one of the following: polymer, polyolefin, polyethylene, polypropylene, ultra-high molecular weight polyethylene (UHMWPE), phenolic resin, polyvinyl chloride (PVC), rubber, synthetic wood pulp (SWP), lignin, glass fiber, synthetic fiber, cellulose fiber, and combinations thereof.

[0212] A fiber mat can be provided. The mat can be one of the following: glass fiber, synthetic fiber, silica, at least one performance-enhancing additive, latex, natural rubber, synthetic rubber, and combinations thereof, and can be nonwoven, mesh, fleece, and combinations thereof.

[0213] In addition, the partition can be a slice, leaf, bag, sleeve, covering, fold, envelope, or hybrid envelope.

[0214] According to at least certain selected exemplary embodiments, the partition may be provided with elastic means for mitigating partition deflection.

[0215] According to at least certain selected embodiments, a lead-acid battery comprises a positive electrode and a negative electrode having a swollen negative electrode active material. A separator is disposed such that at least a portion of the separator is located between the positive and negative electrodes. An electrolyte is provided, which substantially submerges at least a portion of the positive electrode, at least a portion of the negative electrode, and at least a portion of the separator. In at least certain selected embodiments, the separator may have a porous membrane made of at least one polymer and a filler. A first plurality of ribs may extend from the surface of the porous membrane. The ribs may be arranged to prevent acid depletion in the event of NAM swelling. The lead-acid battery can operate under any one or more of the following conditions: in motion, at rest, in standby power applications, in cyclic applications, in a partially charged state, and any combination thereof.

[0216] The ribs can be configured with multiple teeth or discontinuous peaks or protrusions. Each tooth or discontinuous peak or protrusion can be spaced at least about 1.5 mm from another of the multiple discontinuous peaks. A continuous bottom portion can be provided, having multiple teeth or discontinuous peaks or protrusions extending therefrom.

[0217] The first plurality of ribs can be further configured to enhance acid mixing in the battery, particularly during battery operation. The separator can be configured parallel to the battery's start-up and stop movements. The separator may have a pad adjacent to the positive electrode, negative electrode, or the separator itself. This pad can be made at least partially of glass fiber, synthetic fiber, silica, at least one performance-enhancing additive, latex, natural rubber, synthetic rubber, and any combination thereof. The pad can be nonwoven, woven, mesh, fleece, or a combination thereof.

[0218] In at least certain selected embodiments of the present invention, the lead-acid battery may be a flat battery, a flooded lead-acid battery, an enhanced flooded lead-acid battery (EFB), a valve-regulated lead-acid (VRLA) battery, a deep-cycle battery, a gel battery, an absorbent glass mat (AGM) battery, a tubular battery, an inverter battery, a vehicle battery, a start-light-ignition (SLI) vehicle battery, an idle start-stop (ISS) vehicle battery, an automobile battery, a truck battery, a motorcycle battery, an all-terrain vehicle battery, a forklift battery, a golf cart battery, a hybrid electric vehicle battery, an electric vehicle battery, an electric rickshaw battery, or an electric bicycle battery, or any combination thereof.

[0219] In certain implementations, the battery can operate at a depth of discharge between approximately 1% and approximately 99%.

[0220] According to at least one embodiment, a microporous separator with reduced tortuosity is provided. Torque refers to the degree of bending / turning of the pore along its length. Therefore, a microporous separator with reduced tortuosity will provide ions with a shorter path through the separator, thereby reducing electrical resistance. A microporous separator according to such an embodiment may have reduced thickness, increased pore size, more interconnected pores, and / or more open pores.

[0221] According to at least certain selected embodiments, a microporous separator with increased porosity, or a separator with a different pore structure (whose porosity is not significantly different from that of known separators) and / or a reduced thickness is provided. Ions will pass through the microporous separator with optimized porosity, optimized void volume, optimized tortuosity, and / or reduced thickness more rapidly, thereby reducing resistance. Such reduced thickness can reduce the overall weight of the battery separator, thereby reducing the weight of the enhanced flooded battery using such a separator, and consequently reducing the overall weight of the vehicle using such an enhanced flooded battery. Such reduced thickness can also increase the space available for positive electrode active material (PAM) or negative electrode active material (NAM) in the enhanced flooded battery using such a separator.

[0222] According to at least one specific selected embodiment, a microporous separator with increased wettability (in water or acid) is provided. The increased wettability of the separator will make it easier for electrolyte ions to pass through, thereby promoting their passage through the separator and reducing resistance.

[0223] According to at least one embodiment, a microporous separator with reduced final oil content is provided. Such a microporous separator will also help reduce the ER (resistance) in enhanced flooded batteries or systems.

[0224] The separator may contain improved fillers that increase brittleness and can increase the separator's porosity, pore size, internal pore surface area, wettability, and / or surface area. In some embodiments, the improved fillers have a high structural morphology and / or reduced particle size and / or a different amount of silanol groups compared to previously known fillers and / or are more hydroxylated compared to previously known fillers. The improved fillers can absorb more oil and / or allow more processing oil to be incorporated during separator formation without shrinking or compacting during oil removal after extrusion. The fillers can further reduce so-called hydrated spheres of electrolyte ions, enhancing their transmembrane transport, thereby again reducing the total resistance or ER of the battery (e.g., enhanced flooded battery) or system.

[0225] One or more fillers can contain various substances (such as polar materials, like metals) that enhance ion diffusion and facilitate the flow of electrolyte and ions through the separator. When such separators are used in flooded batteries (such as enhanced flooded batteries), this also reduces the overall resistance.

[0226] The microporous separator also features novel and improved pore morphologies and / or novel and improved fiber morphologies, such that when used in flooded lead-acid batteries, the separator helps to significantly reduce the resistance in these batteries. These improved pore and / or fiber morphologies produce separators whose pores and / or fibers approximate a shish-kebab (or shish kabob) type morphology. Another way to describe the novel and improved pore shape and structure is a textured fiber morphology, wherein silica knots or nodules exist at kebab-type configurations on polymer fibers (sometimes referred to as shishes) within the battery separator. Additionally, in certain embodiments, the silica structure and pore structure of the separator according to the invention can be described as a skeletal structure, a columnar structure, or a spinal structure, wherein the silica knots on the polymer kebabs along the polymer fibers resemble columns or discs (kebabs) and are sometimes substantially perpendicular to an elongated central spine or fiber (extended chain-like polymer crystals) that approximates a shish shape.

[0227] In some cases, improved batteries incorporating improved separators with improved pore and / or fiber morphologies can exhibit a 20% (in some cases 25%, and in others 30%) reduction in resistance, and in some cases, even a reduction in resistance (ER) exceeding 30% (which can reduce the battery's internal resistance), while such separators retain and maintain a balance of other key, desired mechanical properties of lead-acid battery separators. Furthermore, in certain embodiments, the separators described herein have novel and / or improved pore shapes, allowing more electrolyte to flow through or fill the pores and / or voids compared to known separators.

[0228] Additionally, this disclosure provides an improved enhanced flooded lead-acid battery comprising one or more improved battery separators for the enhanced flooded battery, the separator combining desired features such as reduced acid stratification, reduced voltage drop (or increased voltage drop durability), and increased CCA (in some cases, the increased CCA is greater than 8%, or greater than 9%, or in some embodiments, greater than 10%, or greater than 15%). This improved separator can produce an enhanced flooded battery with performance matching or even exceeding that of AGM batteries. This low-resistance separator can also be processed to obtain an enhanced flooded lead-acid battery with reduced water consumption.

[0229] The separator may contain one or more performance-enhancing additives (such as surfactants, and other additives or reagents), residual oil, and fillers. These performance-enhancing additives can reduce separator oxidation and / or even further promote ion transmembrane transport, thereby helping to reduce the overall resistance of the enhanced flooded battery described herein.

[0230] The separators for lead-acid batteries described herein may include polyolefin microporous membranes, wherein the polyolefin microporous membranes comprise: a polymer (such as polyethylene, such as ultra-high molecular weight polyethylene), particulate fillers, and processing plasticizers (optionally one or more additional additives or reagents). The polyolefin microporous membrane may include 40% or more of particulate fillers by weight of the membrane. Furthermore, the ultra-high molecular weight polyethylene may comprise a shish-kebab configuration polymer having multiple extended chain crystals (shish configuration) and multiple folded chain crystals (kebab configuration), wherein the average repetition or period of the kebab configuration (at least on the rib side portion of the separator) is from 1 nm to 150 nm, preferably from 10 nm to 120 nm, and more preferably from 20 nm to 100 nm.

[0231] Calculate the average repetition or period of the kebab configuration according to the following definition: After metal vapor deposition, the surface of the polyolefin microporous membrane was observed using a scanning electron microscope (SEM), and then surface images were captured at magnifications of, for example, 30,000 or 50,000 times at an accelerating voltage of 1.0 kV. Within the same visible region of the SEM image, at least three regions are identified, in which the shish-kebab configuration extends continuously with a length of at least 0.5 μm or longer. The kebab period of each identified region is then calculated. The kebab period is determined as follows: a Fourier transform is performed on the concentration distribution (contrast distribution), which is obtained by vertically projecting the shish configuration in the shish-kebab configuration of each marked region, thereby calculating the average repetition period. Use conventional analysis tools, such as MATLAB (R2013a), to analyze the image. In the spectrum obtained after the Fourier transform, the spectrum detected in the short-wavelength region is considered noise. This noise is mainly caused by distortion of the contrast diagram. The contrast distribution of the septum obtained according to the invention appears to produce a square wave (instead of a sine wave). Furthermore, when the contrast distribution is a square wave, the distribution after the Fourier transform becomes a sine function, thus generating multiple peaks in the short-wavelength region in addition to the main peak representing the true kebab period. Such peaks in the short-wavelength region can be detected as noise.

[0232] In some embodiments, the separator for lead-acid batteries described herein has a filler selected from silica, precipitated silica, fumed silica, and precipitated amorphous silica; wherein, through 29 The molecular ratio of OH to Si groups in the filler measured by Si-NMR is in the range of 21:100 to 35:100, in some embodiments 23:100 to 31:100, in some embodiments 25:100 to 29:100, and in some preferred embodiments 27:100 or higher.

[0233] Because the relatively rigid covalent network of Si-O has partially disappeared, the silanol groups transform the silica structure from a crystalline to an amorphous structure. Amorphous silica such as Si(-O-Si)2(-OH)2 and Si(-O-Si)3(-OH) exhibits a wide range of deformations, which can act as different oil absorption points. Therefore, for silica, the oil absorption increases with the amount of silanol groups (Si-OH). Furthermore, when silica has a higher number of silanol groups and / or hydroxyl groups than silica used in known lead-acid battery separators, the separators described herein can exhibit increased hydrophilicity and / or can have a higher porosity and / or can have specific aggregates surrounded by large porosities.

[0234] The microporous separator further comprises new and improved pore morphologies and / or new and improved fiber morphologies, such that when used in a flooded lead-acid battery, the separator helps to significantly reduce the resistance in such a battery. These improved pore and / or fiber morphologies can produce separators whose pores and / or fibers approximate a shish-kebab (or shish kabob) type morphology. Another way to describe the new and improved pore shape and structure is a textured fiber morphology, wherein silica junctions or nodules are present at kebab-type configurations on polymer fibers (sometimes referred to as shishes) within the battery separator. Additionally, in certain embodiments, the silica structure and pore structure of the separator according to the invention can be described as a skeletal structure, a columnar structure, or a spinal structure, wherein the silica junctions along the polymer fibers on the polymer kebabs resemble columns or discs (kebabs) and are sometimes substantially perpendicular to an elongated central spine or fiber (extended chain-like polymer crystals) that approximates a shish shape.

[0235] In certain selected embodiments, the vehicle may be equipped with a lead-acid battery as generally described herein. The battery may further be provided with a separator as described herein. The vehicle may be an automobile, truck, motorcycle, all-terrain vehicle, forklift, golf cart, hybrid vehicle, hybrid electric vehicle battery, electric vehicle, idle start-stop (ISS) vehicle, electric rickshaw, electric bicycle, electric bicycle battery, and combinations thereof.

[0236] In a particular preferred embodiment, this disclosure or invention provides a resilient battery separator whose components, as well as physical properties and characteristics, are synergistically combined to address previously unmet needs in the deep-cycle battery industry in an unexpected way. This separator features an improved battery separator (a separator having a polymer porous membrane such as polyethylene, along with a certain amount of performance-enhancing additives and ribs) that meets or, in certain embodiments, exceeds previously known resilient properties currently used in many deep-cycle battery applications. In particular, the separator of the present invention described herein is more robust, less brittle, less fragile, and more stable over time (less prone to degradation) compared to separators conventionally used with deep-cycle batteries. The resilient, performance-enhancing additive-containing, ribbed separator of the present invention combines the desired robust physical and mechanical properties of polyethylene-based separators with the functionality of conventional separators, while also enhancing the performance of battery systems using such separators.

[0237] According to at least selected embodiments, aspects, or purposes, this document discloses or provides new or improved separators, battery separators, enhanced flooded battery separators, batteries, battery cells, and / or methods of manufacturing and / or using such separators, battery separators, enhanced flooded battery separators, battery cells, and / or batteries. According to at least specific embodiments, this disclosure or invention is directed to new or improved battery separators for enhanced flooded lead-acid batteries. Additionally, this document discloses methods, systems, and battery separators having reduced ER, improved puncture strength, improved separator CMD stiffness, improved oxidation resistance, reduced separator thickness, reduced basis weight, and any combination thereof. According to at least particular embodiments, this disclosure or invention is directed to improved separators for enhanced flooded lead-acid batteries, wherein the separator has reduced ER, improved puncture strength, improved separator CMD stiffness, improved oxidation resistance, reduced separator thickness, reduced basis weight, or any combination thereof. According to at least certain embodiments, a separator is provided that includes or exhibits reduced ER, improved puncture strength, improved separator CMD stiffness, improved oxidation resistance, reduced separator thickness, reduced basis weight, and any combination thereof. According to at least certain embodiments, a separator is provided for battery applications, including flat-plate batteries, tubular batteries, vehicle SLI and HEV ISS applications, deep-cycle applications, golf cart or golf wheelchair batteries, batteries operating at partial state of charge (PSOC), inverter batteries, and batteries for renewable energy, and any combination thereof.

[0238] In a particular exemplary embodiment, the lead-acid battery is provided with an electrode array having one or more negative electrodes and one or more positive electrodes interleaved between the one or more negative electrodes. At least one of the one or more negative electrodes is encapsulated by a fiber pad, while one or more positive electrodes adjacent to at least one of the one or more negative electrodes are encapsulated by a porous membrane. The porous membrane may be a microporous battery separator.

[0239] In an exemplary aspect, the fiber mat can be nonwoven, mesh, felt, and / or combinations thereof. The fiber mat can also be glass fiber, pulp, polymer, and / or combinations thereof. Additionally, the fiber mat can be formed from a polymer along with additional glass fiber, pulp, and / or combinations thereof, and the polymer can be polyolefin, polyester, polyamide, polyimide, and / or combinations thereof. The fiber mat can be an inorganic material, such as silica. The fiber mat is a spunbond melt nonwoven composite or a carbon fiber nonwoven material and / or the like.

[0240] An exemplary porous membrane may be provided with one or more sets of ribs on at least one surface, or one or more sets of ribs on both surfaces. The ribs may have a height of about 10 μm to about 2.0 mm. The porous membrane may be one or more of natural materials, synthetic materials, polyolefins, phenolic resins, polyvinyl chloride (PVC), natural rubber, synthetic rubber, synthetic wood pulp, glass fiber, lignin, cellulose fibers, and / or combinations thereof. Alternatively, the porous membrane may be polyethylene, silica, and processing oil, wherein the amount of processing oil is about 5% to about 15% of the weight of the porous membrane.

[0241] In specific selected aspects, the porous membrane has a porosity greater than about 55%, about 60%, and about 65%.

[0242] In another exemplary aspect, the porous membrane of the exemplary lead-acid battery may be encapsulated around the positive electrode and sealed on one, two, and / or three sides of the positive electrode.

[0243] In yet another exemplary aspect, the fiber pad of the exemplary lead-acid battery may be encapsulated around the negative electrode and sealed on one, two, and / or three sides of the negative electrode.

[0244] In yet another exemplary embodiment, a preferred example of a lead-acid battery may be provided with an electrode array including one or more negative electrodes and one or more positive electrodes interspersed between the one or more negative electrodes. The battery may further include one or more electrode and fiber pad assemblies, comprising a fiber pad at least partially integrated into at least one negative electrode. A porous membrane (which may be a microporous membrane) may encapsulate one or more of the one or more electrode and fiber pad assemblies, or may encapsulate at least one of the one or more positive electrodes adjacent to the one or more electrode and fiber pad assemblies. In an exemplary aspect, the fiber pad may be integrated into the active material at about 2% to about 50% of the fiber pad thickness, about 5% to about 25% of the pad thickness, about 5% to about 20% of the pad thickness, or about 10% to about 15% of the pad thickness.

[0245] Any exemplary fiber mat can be one or more of nonwoven materials, meshes, felts, and / or combinations thereof. Additionally, the fiber mat can be one or more of glass fibers, pulp, polymers, and / or combinations thereof. Further, the fiber mat can be formed from polymers and polymers combined with additional glass fibers, pulp, and / or combinations thereof, and the polymer can be one or more of polyolefins, polyesters, polyamides, polyimides, and / or combinations thereof.

[0246] In another aspect of the exemplary lead-acid battery, the exemplary fiber pad can be an inorganic material, such as silica. The fiber pad can be spunbond melt nonwoven fabric, carbon fiber nonwoven fabric, and / or the like.

[0247] In another aspect of the exemplary lead-acid battery, the exemplary porous membrane may have one or more sets of ribs on one or both of its surfaces. The ribs in the one or more sets of ribs may have a height of about 10 μm to about 2.0 mm.

[0248] Exemplary porous membranes may be at least one of natural materials, synthetic materials, polyolefins, phenolic resins, polyvinyl chloride (PVC), natural rubber, synthetic rubber, synthetic wood pulp, glass fiber, lignin, cellulose fiber, and / or combinations thereof. In a particular embodiment, the porous membrane may be polyethylene, silica, and processing oil.

[0249] In another exemplary aspect, the porous membrane of the exemplary lead-acid battery may be encapsulated around the positive electrode and sealed on one, two, and / or three sides of the positive electrode. In yet another exemplary aspect, the porous membrane of the exemplary lead-acid battery may be sealed on one, two, and / or three sides of one or more electrode and fiber pad assemblies.

[0250] In a further selected embodiment of the exemplary preferred embodiment, the lead-acid battery is provided with an electrode array consisting of one or more negative electrodes and one or more positive electrodes arranged alternately with each other. A porous membrane encapsulation is further provided to encapsulate at least one of the one or more negative electrodes located therein. The porous membrane includes ribs on one or more surfaces, and a fiber pad is located within the encapsulation. The ribs may be at least partially on the surface of the porous membrane adjacent to the fiber pad. The ribs may have a height of about 10 μm to about 2.0 mm, about 5 μm to about 300 μm, or about 25 μm to about 200 μm. Additionally, the fiber pad may encapsulate at least one of the one or more negative electrodes. Further, the fiber pad may be at least partially integrated into the negative electrode.

[0251] As an alternative, the fiber pad can be a discrete element located between the ribs and has a thickness of about 50% to about 150% of the rib height. In selected aspects of the invention, the fiber pad can be located between the negative electrode and the porous membrane. The fiber pad can be one or more of glass fibers, pulp, polymers, and combinations thereof. The fiber pad can be formed from a polymer combined with one or more of glass fibers, pulp, and combinations thereof; wherein the polymer can be one or more of polyolefins, polyesters, polyamides, polyimides, and combinations thereof. Alternatively, the fiber pad can be an inorganic material, such as silica. The fiber pad can be a spunbond melt nonwoven composite material or a carbon fiber nonwoven material.

[0252] In selected embodiments, the porous membrane may have ribs on both of its surfaces. Furthermore, the porous membrane may be one or more of natural materials, synthetic materials, polyolefins, phenolic resins, polyvinyl chloride (PVC), natural rubber, synthetic rubber, synthetic wood pulp, glass fiber, lignin, cellulose fibers, and combinations thereof. Specifically, the porous membrane may be polyethylene, silica, and processing oils.

[0253] In a selected aspect of the invention, the porous membrane can be sealed on one side, two sides, or three sides of the negative electrode. Alternatively, a fiber pad can be sealed on one side, two sides, or three sides of the negative electrode.

[0254] In selected embodiments of the invention, a system is configured to provide a vehicle that utilizes one or more batteries as fully described herein. The vehicle may be an automobile, truck, motorcycle, all-terrain vehicle, motorbike, forklift, golf cart, hybrid vehicle, hybrid electric vehicle, electric vehicle, idle start-stop (ISS) vehicle, electric rickshaw battery, electric tricycle, electric bicycle, wheelchair, or boat.

[0255] In selected embodiments, the lead-acid battery as fully described herein can be a flat battery, a flooded lead-acid battery, an enhanced flooded lead-acid battery (EFB), a valve-regulated lead-acid (VRLA) battery, a gel battery, an absorbent glass mat (AGM) battery, a deep-cycle battery, a tubular battery, an inverter battery, a vehicle battery, a start-light-ignition (SLI) vehicle battery, an idle-start-stop (ISS) vehicle battery, an automobile battery, a truck battery, a motorcycle battery, an all-terrain vehicle battery, a forklift battery, a golf cart battery, a hybrid electric vehicle battery, an electric vehicle battery, a wheelchair battery, an electric rickshaw battery, an electric tricycle battery, an electric bicycle battery, or a marine battery.

[0256] In selected embodiments, a method is provided for preventing or mitigating acid displacement in lead-acid batteries, flooded lead-acid batteries, or flooded lead-acid batteries operating in or to be operated in a partially charged state. This method may include manufacturing a battery having a structure substantially the same as any battery described herein.

[0257] New or improved systems, vehicles, batteries, enhanced flooded lead-acid batteries, deep-cycle batteries, separators, battery separators, enhanced flooded lead-acid battery separators, deep-cycle battery separators, separators, fiber pads, battery cells, electrodes, and / or methods of manufacturing and / or using such batteries, enhanced flooded lead-acid batteries, deep-cycle batteries, separators, battery separators, enhanced flooded lead-acid battery separators, deep-cycle battery separators, fiber pads, battery cells, and / or electrodes as described or demonstrated herein.

[0258] New or improved batteries, particularly lead-acid batteries as shown and / or described herein; new or improved systems, vehicles, batteries, enhanced flooded lead-acid batteries, deep-cycle batteries, separators, battery separators, enhanced flooded lead-acid battery separators, deep-cycle battery separators, separators, fiber pads, battery cells, electrodes, and / or methods of manufacturing and / or using such systems, vehicles, batteries, enhanced flooded lead-acid batteries, deep-cycle batteries, separators, battery separators, enhanced flooded lead-acid battery separators, deep-cycle battery separators, separators, fiber pads, battery cells, and / or electrodes; improved batteries having improved separators for lead-acid batteries, and / or improved methods of using such batteries having such improved separators; methods, systems, processes, and battery separators used to extend battery life, reduce battery failure, reduce water consumption, reduce float charge current, reduce increase in internal resistance, improve wettability, reduce acid stratification, and improve acid diffusion in lead-acid batteries. Retaining active materials, reducing active material shedding and / or improving uniformity; improved separators for lead-acid batteries, wherein the separators include improved functional coatings, improved battery separators that reduce acid stratification, improved battery separators that improve acid diffusion, improved lead-acid batteries that retain active materials, improved lead-acid battery separators that reduce active material shedding, improved lead-acid batteries including such improved separators, long-life automotive lead-acid batteries, improved flooded lead-acid batteries and / or the like, and / or batteries having reduced acid stratification, improved acid diffusion, improved active material retention capacity and / or increased ability to reduce active material shedding; a battery having a polyethylene separator and a negative electrode with a fiber pad disposed therebetween, and / or a method of manufacturing and / or using such a battery; a battery having a porous membrane and a fiber pad laminated thereon, wherein in such a battery the fiber pad is adjacent to the negative electrode, and / or a method of manufacturing and / or using such a battery. In certain embodiments, it may be preferred that the fiber pad is bonded to the polymer membrane (e.g., bonded to a rib of the membrane, such as a negative electrode rib), and the fiber pad is not embedded in the back mesh of the membrane.

[0259] As described herein, the exemplary separator can be used in lead-acid batteries for a variety of applications. Such applications may include, for example: partial state-of-charge applications; deep cycle applications; automotive applications; truck applications; motorcycle applications; mobility-powered applications, such as forklifts, golf carts, etc.; electric vehicle applications; hybrid electric vehicle (HEV) applications; ISS vehicle applications; rickshaw applications; electric tricycle applications; electric bicycle applications; marine applications; and energy harvesting and storage applications, such as renewable and / or alternative energy harvesting and storage, such as wind and solar power. Furthermore, the exemplary separator can be used in a variety of batteries. Such exemplary batteries may include, for example: flooded lead-acid batteries, such as enhanced flooded lead-acid batteries; AGM batteries; VRLA batteries; flat batteries; tubular batteries; partially charged batteries; deep-cycle batteries; automotive batteries; truck batteries; motorcycle batteries; mobile power batteries, such as forklift batteries, golf cart batteries, etc.; electric vehicle batteries; hybrid electric vehicle (HEV) batteries; ISS vehicle batteries; electric rickshaw batteries; electric tricycle batteries; electric bicycle batteries; marine batteries; energy harvesting and storage batteries, such as renewable and / or alternative energy harvesting and storage, such as wind power, solar power, etc.

[0260] According to at least selected embodiments, this disclosure or invention is dedicated to new or improved separators for use in lead-acid batteries, such as flooded lead-acid batteries, particularly enhanced flooded lead-acid batteries (EFB), and various other lead-acid batteries, such as gel and absorbent glass mat (AGM) batteries. According to at least selected embodiments, this disclosure or invention is dedicated to new or improved separators, battery separators, resilient separators, balancing separators, EFB separators, batteries, battery cells, systems, methods relating to them, vehicles using them, methods of manufacturing them, their applications, and combinations thereof. Additionally, methods, systems, and battery separators disclosed herein extend battery life and reduce battery failure by reducing acid deficiency at the battery electrodes.

[0261] This document describes flooded lead-acid batteries and vehicles incorporating such batteries. Flooded lead-acid batteries include an electrode array comprising one or more negative electrode plates and one or more positive electrode plates, which are arranged alternately and interspersed with each other. In some embodiments, the negative electrode plates are wrapped or encapsulated by fiber pads, and a porous membrane is wrapped or encapsulated around adjacent positive electrode plates. In some embodiments, the fiber pads are at least partially integrated into the negative electrode plates, and the porous membrane is either wrapped around the negative electrode plates in which the fiber pads are partially integrated, or wrapped around adjacent positive electrode plates. In other embodiments, the negative electrode plates are encapsulated by a ribbed porous membrane, and a fiber pad exists between the encapsulated negative electrode plate and the porous membrane encapsulating the negative electrode plate. Methods, systems, and vehicles utilizing the disclosed battery are also provided.

[0262] According to at least selected embodiments, this disclosure or invention is directed to new or improved separators, battery separators, enhanced flooded battery separators, batteries, battery cells, and / or methods of manufacturing and / or using such separators, battery separators, enhanced flooded battery separators, battery cells, batteries, systems, methods, and / or vehicles using them. According to at least specific embodiments, this disclosure or invention is directed to new or improved battery separators, resilient separators, balancing separators, flooded lead-acid battery separators, or enhanced flooded lead-acid battery separators, such as separators for deep cycling and / or partial state-of-charge (PSoC) applications. Such applications may include, but are not limited to, the following: electromechanical applications, such as forklifts and golf carts (sometimes referred to as golf carts), electric rickshaws, electric bicycles, electric tricycles, etc.; automotive applications, such as start-light-ignition (SLI) batteries, such as batteries for internal combustion engine vehicles; idle start-stop (ISS) vehicle batteries; hybrid vehicle applications, hybrid electric vehicle applications; batteries with high power requirements, such as uninterruptible power supplies (UPS) or valve-regulated lead-acid (VRLA) and / or batteries with high CCA requirements; inverters; and energy storage systems, such as those found in renewable and / or alternative energy systems (such as solar and wind energy harvesting systems).

[0263] According to at least selected embodiments, this disclosure or invention is directed to separators, elastic separators, balancing separators, particularly separators for flooded lead-acid batteries, which are capable of reducing or mitigating acid deficiency; reducing or mitigating acid stratification; reducing or mitigating dendrite growth; having reduced resistance and / or being able to increase cold start current; having reduced resistance and negative electrode cross ribs; having low water consumption, reduced resistance and / or negative electrode cross ribs; having properties, features and / or structures that inhibit or prevent dendrite growth; having anti-acid mixing properties, features and / or structures; having reinforced negative electrode cross ribs; having glass pads on the positive and / or negative electrode sides of PE films, sheets, sleeves, folds, wraps, bags, covers and / or the like; having glass pads laminated to PE films and / or combinations or sub-combinations thereof.

[0264] This document discloses an improved separator for a lead-acid battery, an improved lead-acid battery incorporating such an improved separator, and exemplary embodiments of systems or vehicles incorporating such an improved separator and / or battery. The lead-acid battery separator comprises a porous membrane having multiple ribs extending from its surface. The ribs are provided with multiple discontinuous peaks, arranged such that the porous membrane provides elastic support to resist forces exerted by NAM swelling, thereby mitigating the effects of acid deficiency associated with NAM swelling. The separator is also configured to utilize any movement experienced by the battery incorporating such a separator to mitigate the effects of acid stratification by promoting acid mixing. A lead-acid battery incorporating the provided separator is also provided. Such a lead-acid battery can be a flooded lead-acid battery, an enhanced flooded lead-acid battery, and can be configured to operate in a partially charged state. Systems incorporating such a lead-acid battery, such as vehicles or any other energy storage systems, such as solar or wind power harvesting systems, are also provided. Other exemplary implementations are provided, such as having any one or more of the following: reduced resistance; enhanced puncture resistance; enhanced oxidation resistance; improved ability to mitigate the effects of dendrite growth; and other improvements.

[0265] According to at least selected embodiments, aspects, or purposes, this disclosure or invention can solve problems or difficulties of existing batteries, separators, or membranes (particularly, but not limited to, EFB batteries and separators), and / or can provide and / or can be committed to new or improved separators, battery separators, membranes, separator membranes, enhanced flooded battery separators, fiber pads, batteries, battery cells, and / or methods of manufacturing and / or using such separators, battery separators, fiber pads, enhanced flooded battery separators, battery cells, and / or batteries. According to at least specific embodiments, this disclosure or invention is committed to new or improved enhanced flooded lead-acid battery separators and fiber pads for start-up lighting ignition (SLI) batteries, flooded batteries and / or enhanced flooded batteries and / or systems for deep-cycle applications, vehicles, and / or the like (which include such separators, pads, and batteries), and / or improved methods of manufacturing and / or using such improved separators, pads, battery cells, batteries, systems, vehicles, and / or the like. According to at least certain embodiments, this disclosure or invention is dedicated to improved separators for enhanced flooded batteries and / or improved methods of manufacturing and / or using such batteries having such improved separators. According to at least selected embodiments, this disclosure or invention is dedicated to separators, particularly separators for enhanced flooded batteries, having reduced resistance and / or increased cold-start current. Additionally, methods, systems, and battery separators are disclosed herein for enhancing the retention of active materials, extending battery life, reducing water consumption, reducing internal resistance, increasing wettability, reducing acid stratification, improving acid diffusion, improving cold-start current, improving uniformity, etc., in at least enhanced flooded batteries. According to at least particular embodiments, this disclosure or invention is dedicated to improved separators for enhanced flooded batteries, wherein the separator comprises one or more performance-enhancing additives or coatings, increased porosity, increased pore volume, amorphous silica, silica with higher oil absorption, silica with higher silanol groups, retention of active materials on electrodes, and / or improved retention and / or any combination thereof.

[0266] According to at least certain embodiments, this disclosure or invention is directed to new or improved separators, battery separators, flooded battery separators, enhanced flooded battery separators, fiber pads, batteries, battery cells, and / or methods of manufacturing and / or using such separators, battery separators, fiber pads, flooded battery separators, enhanced flooded battery separators, battery cells, and / or batteries. According to at least certain embodiments, this disclosure or invention is directed to new or improved enhanced flooded battery separators and fiber pads for start-up lighting ignition (SLI) batteries, flooded batteries for deep-cycle applications, flooded batteries for mobile power applications, flooded batteries for partial state-of-charge (PSoC) applications, and / or enhanced flooded batteries and / or systems, vehicles, and / or the like, which include such separators, fiber pads, batteries, and / or improved methods of manufacturing and / or using such improved separators, fiber pads, battery cells, batteries, systems, vehicles, and / or the like. According to at least certain embodiments, this disclosure or invention is dedicated to improved separators for enhanced flooded batteries and / or improved methods of manufacturing and / or using such batteries having such improved separators. According to at least selected embodiments, this disclosure or invention is dedicated to separators, particularly for enhanced flooded batteries, having reduced resistance and / or increased cold-start current. Additionally, methods, systems, and battery separators are disclosed herein for enhancing the retention of active materials, extending battery life, reducing water consumption, reducing internal resistance, increasing wettability, reducing acid stratification, improving acid diffusion, improving cold-start current, and improving uniformity in at least enhanced flooded batteries and / or the like. According to at least particular embodiments, this disclosure or invention is dedicated to improved separators for enhanced flooded batteries, wherein the separator comprises one or more performance-enhancing additives or coatings, optimized porosity, optimized void volume, amorphous silica, silica with higher oil absorption, silica with higher silanol groups, retention of active materials on electrodes, and / or improved retention and / or any combination thereof.

[0267] According to at least one particular embodiment, this disclosure or invention is dedicated to improved separators for flooded or enhanced flooded batteries, wherein the separators include improved formulations designed to further reduce water consumption, reduce maintenance, and increase abuse tolerance in heavy-duty deep-cycle applications such as golf carts, renewable energy systems, floor machinery, and traction vehicles. Features may include: It contains a new polyethylene formulation that counteracts the effects of antimony migration. Its inhibitory effect is comparable to that of rubber separators. For encapsulation or sealing automation, it is sealable, thus providing short-circuit protection. High antioxidant properties High porosity allows for lower electrical resistance. Optional glass pads for retaining active materials Advantages may include: By offsetting the negative effects of antimony poisoning (including excellent antioxidant properties and reduced water consumption), it exceeds the requirements for battery life. Encapsulation and sealing on high-speed equipment can improve production efficiency and consistency, while reducing field failures. According to at least other specific embodiments, this disclosure or invention is dedicated to improved separators for tubular, flooded, or enhanced flooded batteries, wherein the separator, through special water-reducing features and a unique profile design, helps extend battery life in mobile power applications. With the increasing prevalence of mobile power batteries operating in a partially charged state, this separator can help prevent accelerated grid corrosion and acid stratification, thereby extending battery life.

[0268] Features may include: Serrated rib pattern Low water consumption performance Closer rib spacing Advantages may include: Enhances acid cycling and improves acid mixing (reduces acid stratification). Lower acid displacement Reduce water consumption The plates are evenly spaced and will not move upwards under vibration. Uniform component compression results in closer rib spacing.

[0269] In selected embodiments, this document describes a flooded lead-acid battery and a system, vehicle, or apparatus including the flooded lead-acid battery. In a particular selected embodiment, the flooded lead-acid battery includes an electrode array comprising one or more negative electrode plates and one or more positive electrode plates, which are arranged alternately and interlaced with each other. In some embodiments, the negative electrode plate is wrapped or encapsulated by a fiber pad, and a porous membrane is wrapped or encapsulated around an adjacent positive electrode. In some embodiments, the fiber pad is at least partially integrated into the negative electrode plate, and the porous membrane is either wrapped around a negative electrode plate in which the fiber pad is partially integrated, or wrapped around an adjacent positive electrode plate. In other embodiments, the negative electrode plate is encapsulated by a ribbed porous membrane, and a fiber pad exists between the encapsulated negative electrode plate and the porous membrane encapsulating the negative electrode plate. In some embodiments, the positive electrode plate is wrapped or encapsulated by a fiber pad, and a porous membrane is wrapped or encapsulated around an adjacent negative electrode. In some embodiments, a fiber pad is at least partially integrated into the positive electrode plate, and a porous membrane is either wrapped around the positive electrode plate in which the fiber pad is partially integrated, or wrapped around an adjacent negative electrode plate. In other embodiments, the positive and / or negative electrode plates are encapsulated by a ribbed porous membrane, and a fiber pad exists between the encapsulated positive and / or negative electrode plates and the porous membrane encapsulating the positive and / or negative electrode plates. In certain embodiments, methods, systems, devices, and / or vehicles are also provided that utilize the disclosed separators, electrodes, pads, membranes, composite pads and membranes, laminated pads and membranes, encapsulated electrodes, bagged electrodes, encapsulated and bagged electrodes, and / or batteries.

[0270] According to at least selected embodiments, this disclosure or invention is directed to separators for lead-acid batteries (particularly flooded lead-acid batteries) and various lead-acid batteries having such separators, such as flooded lead-acid batteries or enhanced flooded lead-acid batteries. According to at least selected embodiments, this disclosure or invention is directed to new or improved separators, battery cells, batteries, and / or methods of manufacturing and / or using such separators, battery cells, and / or batteries. According to at least specific embodiments, this disclosure or invention is directed to improved separators for lead-acid batteries and / or improved methods of using such batteries having such improved separators. Such batteries can be 6-volt (or 6V) or 12-volt batteries, 12, 18, 24, 30, 36, 42, or 48-volt battery packs, 24-volt, 36-volt, 48-volt, 60-volt, 72-volt, or 84-volt batteries or battery packs, connected in series, connected in parallel, battery strings of two or more batteries, and / or the like. Such lead-acid batteries can be used in combination with one or more capacitors, lithium batteries, fuel cells, and / or the like. Such batteries and battery combinations can be used in a variety of exemplary applications, such as in vehicles, in alternative energy harvesting and storage (e.g., those used in solar and wind power harvesting and other renewable and / or alternative energy sources), inverters, uninterruptible power supply (UPS) equipment, and / or the like. Additionally, methods, systems, and battery separators disclosed herein are used to enhance the retention of active materials in lead-acid batteries, extend battery life, reduce battery failure, reduce water consumption, improve oxidation stability, improve, maintain, and / or reduce float charge current, improve end-of-charge (EOC) current, reduce the current and / or voltage required for deep-cycle charging and / or full charging of batteries, minimize the increase in internal resistance, reduce resistance, increase wettability, reduce electrolyte wetting time, reduce battery formation time, reduce antimony poisoning, reduce acid stratification, improve acid diffusion, and / or improve uniformity. According to at least a particular embodiment, this disclosure or invention is dedicated to improved separators for lead-acid batteries, wherein the separator includes one or more improved performance-enhancing additives and / or coatings. According to at least certain embodiments, the disclosed separator can be used in deep-cycle applications, such as in mobile machinery or vehicles and / or stationary machinery or vehicles, like golf carts, forklifts, inverters, renewable energy systems and / or alternative energy systems (by way of example only, such as solar power systems and wind power systems); in particular, the disclosed separator can be used in battery systems where deep-cycle and / or partial-charge operation is part of the battery life; and even more particularly, in battery systems in which additives and / or alloys [e.g., antimony (Sb)] are added to the battery to extend battery life and / or enhance battery performance and / or enhance the battery's ability to operate in deep-cycle and / or partial-charge states.

[0271] The composition and methods of the appended claims are not limited in scope to the specific compositions and methods described herein, which are intended to illustrate several aspects of the claims, and any functionally equivalent compositions and methods are intended to fall within the scope of the claims. Various variations of compositions and methods, in addition to those shown and described herein, are also intended to fall within the scope of the appended claims. Furthermore, although only specific representative compositions and method steps disclosed herein are specifically described, other combinations of compositions and method steps are intended to fall within the scope of the appended claims, even if not specifically stated. Thus, combinations of steps, elements, components, or ingredients may be explicitly or less explicitly referred to herein, but other combinations of steps, elements, components, and ingredients are included even if not explicitly stated. When used herein, the term “comprising” and variations thereof are used synonymously with the term “including” and variations thereof and are open-ended, non-limiting terms. Although the terms “comprising” and “including” have been used herein to describe various embodiments, the terms “consistently composed of” and “comprises” may be used instead of “comprising” and “including” to provide more specific embodiments of the invention, which are also disclosed. Except as described in the embodiments or otherwise, all figures used in the specification and claims to indicate quantities of ingredients, reaction conditions, etc., should be understood at least as not an attempt to limit the application of the doctrine of equivalence to the scope of the claims, and should be interpreted in accordance with the number of significant figures and conventional rounding methods.

[0272] The invention may be implemented in other forms without departing from its spirit and essential attributes; therefore, when specifying the scope of the invention, reference should be made to the appended claims rather than the foregoing description. Disclosed are components that can be used to perform the disclosed methods and systems. These and other components are disclosed herein, and it should be understood that while specific references to combinations and arrangements of each individual and collective may not be explicitly disclosed when disclosing combinations, subsets, interactions, groups, etc., of these components, each is specifically considered and described herein for all methods and systems. This applies to all aspects of this application, including but not limited to the steps in the disclosed methods. Therefore, if multiple additional steps can be performed, it should be understood that each of these additional steps can be performed in conjunction with any specific embodiment or combination of embodiments of the disclosed method.

[0273] The foregoing written description of the structures and methods is given for illustrative purposes only. The embodiments are used to disclose exemplary implementations, including best practices, and also to enable any person skilled in the art to practice the invention, including making and using any device or system and performing any combined methods. These embodiments are not intended to be exhaustive or to limit the invention to the precise steps and / or forms disclosed, and many modifications and variations are possible in light of the above teachings. The features described herein can be combined in any combination. The steps of the methods described herein can be performed in any physically possible order. The patentable scope of the invention is defined by the appended claims and may include other embodiments that would occur to a person skilled in the art. Such other embodiments are intended to be within the scope of the claims if they have structural elements that do not differ from the literal language of the claims, or if they include equivalent structural elements that do not substantially differ from the literal language of the claims.

[0274] The composition and methods of the appended claims are not limited in scope to the specific compositions and methods described herein (which are intended as descriptions of some aspects of the claims). Any functionally equivalent compositions and methods are intended to fall within the scope of the claims. Various variations of compositions and methods, in addition to those shown and described herein, are also intended to fall within the scope of the appended claims. Furthermore, although only specific representative compositions and method steps disclosed herein are specifically described, other combinations of compositions and method steps are intended to fall within the scope of the appended claims, even if not specifically stated otherwise. Thus, combinations of steps, elements, components, or ingredients may be explicitly or less explicitly referred to herein; however, other combinations of steps, elements, components, and ingredients are included even if not explicitly stated otherwise.

[0275] When used in the specification and appended claims, the singular forms “a,” “an,” and “the” include plural references unless the context clearly indicates otherwise. A range may be expressed herein as from “about” or “approximately” one particular value and / or to “about” or “approximately” another particular value. When such a range is expressed, another embodiment includes from one particular value and / or to another particular value. Similarly, when a value is expressed as an approximation using the antecedent “about,” it will be understood that the particular value forms another embodiment. It should also be understood that the endpoints of each range are significant both relative to and independent of the other endpoint. “Optional” or “optionally” means that the event or condition subsequently described may or may not occur, and the description includes both scenarios in which the event or condition occurs and scenarios in which it does not occur.

[0276] Throughout this specification and claims, the word “comprising” and variations thereof, such as “comprising in participle” and “comprising in singular,” means “including, but not limited to,” and is not intended to exclude, for example, other additives, components, integers, or steps. The terms “consistently of” and “comprises of” may be used in place of “comprising” and “including” to provide more specific embodiments of the invention, and are also disclosed. “Exemplary” or “for example” means “an example of” and is not intended to convey indications of preferred or ideal embodiments. Similarly, “for example” is not limiting but is used for explanatory or exemplary purposes.

[0277] Unless otherwise stated, all figures used in the specification and claims to indicate geometry, dimensions, etc., should be understood at least as not an attempt to limit the application of the doctrine of equivalence to the scope of the claims, and should be interpreted in accordance with the number of significant figures and conventional rounding methods.

[0278] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which the disclosed invention pertains. Publications cited herein and the material cited therein are expressly incorporated by reference. Furthermore, the invention disclosed herein may be practiced in the absence of any elements not specifically disclosed herein.

Claims

1. A battery separator or storage battery separator, comprising: A microporous packing membrane having a back mesh having a first surface, a second surface, and a back mesh thickness defined as the distance between the first surface and the second surface; The partition has at least two, at least three, or at least four of the following characteristics: Porosity greater than 50%-65% or greater than 50%-60%; Total thickness of partitions: approximately 0.15 mm to approximately 2.5 mm, approximately 0.25 mm to approximately 2.25 mm, approximately 0.5 mm to approximately 2.0 mm, approximately 0.5 mm to approximately 1.5 mm, approximately 0.75 mm to approximately 1.5 mm, approximately 0.8 mm, or approximately 1.1 mm. Oil content reduction of less than 19% by weight; and Average pore size not greater than 1 μm.

2. The battery separator or storage battery separator as described in claim 1, wherein, The filler membrane is a silica filler membrane; the filler membrane is filled with at least one filler with a high structural morphology selected from silica, dry-processed fine silica, precipitated silica, amorphous silica, highly brittle silica, alumina, talc, fish meal, fish bone meal, carbon, and carbon black; and / or the microporous filler membrane is flat, grooved, textured, or raised; A first set of ribs extends from the first surface; a second set of ribs extends from the second surface; the rib width in the first set of ribs and / or the second set of ribs is at least about 0.005 mm, 0.01 mm, 0.025 mm, 0.05 mm, 0.075 mm, 0.1 mm, 0.2 mm, 0.3 mm, 0.4 mm, 0.5 mm, 0.6 mm, 0.7 mm, 0.8 mm, 0.9 mm, 1.0 mm, 1.1 mm, 1.2 mm, 1.3 mm, 1.4 mm, or 1.5 mm; and / or, the rib width in the second set of ribs is not greater than 100 μm; At least one surface of the microporous filler membrane has ribs; and / or the ribs have a width between approximately 0.005-1.5 mm, 0.01-1.0 mm, 0.025-1.0 mm, 0.05-1.0 mm, 0.075-1.0 mm, 0.1-1.0 mm, 0.2-1.0 mm, 0.3-1.0 mm, 0.4-1.0 mm, 0.5-1.0 mm, 0.4-0.8 mm, or 0.4-0.6 mm. The first group of ribs or the second group of ribs is selected from: uninterrupted ribs, discrete discontinuous ribs, continuous ribs, discontinuous ribs, angular ribs, linear ribs, longitudinally extending ribs, transverse ribs, transverse ribs, intersecting ribs, discrete toothed or serrated ribs, serrated protrusions, serrated ribs, micro ribs, intersecting micro ribs or stacked protrusions or stacked ribs, curved or sinusoidal ribs, acid-mixed ribs, and combinations thereof. The partition has a reduced oil content of less than 10% by weight, or the partition has a reduced oil content of less than 5% by weight. The partition includes fibers or fiber pads, the fiber pads serving as a carrier for additional materials, and / or the additional materials are selected from: rubber, latex, silica, one or more performance-enhancing additives, and combinations thereof; The battery separator is in the form of a bag, sleeve or wrapping, and / or is sealed along at least one, at least two or at least three edges. Preferably, the sealing method is at least one of the following: adhesive, heat (melt) sealing, mechanical sealing, ultrasonic sealing, compression, welding or a combination thereof. The separator includes one or more performance-enhancing additives and / or coatings, optimized porosity, optimized void volume, amorphous silica, silica with higher oil absorption, silica with higher silanol groups, retention and / or improved retention of active materials on the electrode, and / or any combination thereof. The battery separator has a structure, additives, or coating to reduce acid stratification, improve acid diffusion, retain active materials, and reduce active material shedding, thereby providing a long-life battery and a battery that reduces acid stratification, improves acid diffusion, enhances the ability to retain active materials, and / or enhances the ability to reduce active material shedding. The separator has a fiber pad on at least one side, and / or has a fiber pad laminated on the separator, especially the laminated fiber pad is adjacent to the positive or negative electrode; The microporous filler membrane has a coating on a first surface and / or a second surface, the coating comprising silica and an adhesive; The membrane is sealed in one of the following ways, selected from: sealing on one side of the positive electrode, sealing on both sides of the positive electrode, and sealing on three sides of the positive electrode; The partition has a fiber pad sleeve that is sealed in one of the following ways, selected from: sealing on one side of the negative electrode, sealing on both sides of the negative electrode, or sealing on three sides of the negative electrode. The membrane is made of the following materials: a natural or synthetic substrate, a processing plasticizer, a filler, one or more natural or synthetic rubbers and / or latexes, one or more other additives and / or coatings, and any combination thereof; the one or more rubbers and / or latexes may be cured or cross-linked, or uncured or uncross-linked; One or more other additives, such as surfactants, antioxidants, etc.; The membrane may contain additives, including surfactants, wetting agents, colorants, antistatic additives, antioxidants, and combinations thereof; The membrane is made of materials selected from: polymers, thermoplastic polymers, thermoplastic polymers such as acid-resistant thermoplastic materials, polyethylene compounds, polyolefins, polyvinyl chloride (PVC), polyethylene, ultra-high molecular weight polyethylene (UHMWPE), polypropylene, fillers (such as silica) and mixtures of UHMWPE, rubber, synthetic wood pulp (SWP), lignin, glass fiber, synthetic fiber, cellulose fiber, and combinations thereof. The separator is in the form of a bag, a cover, or a package, and the battery includes an electrode, wherein the bag, cover, or package structure contains one electrode; The separator is in the form of a bag, a cover, or a package; the battery includes a positive electrode and a negative electrode; and the bag, cover, or package structure includes a negative electrode; and / or The separator is in the form of a bag, a cover, or a wrapping, and the outer side of the structure is coated. The battery includes a positive electrode and a negative electrode, and the bag, cover, or wrapping structure contains a negative electrode.

3. A battery or accumulator comprising the battery separator or accumulator separator as described in claim 1.

4. The battery or accumulator as described in claim 3, wherein, The partition has the following characteristics: a porosity greater than 50%-60%; a reduction in oil content of less than 5% by weight; a total partition thickness of no more than 1.5 mm; and an average pore size of no more than 1 μm.

5. A battery or accumulator comprising an electrode array including one or more negative electrodes and one or more positive electrodes alternating with said one or more negative electrodes, wherein, The negative electrode plate is wrapped or encapsulated by a fiber pad, while the porous membrane is wrapped or encapsulated by the adjacent positive electrode; or The fiber pad is at least partially integrated into the negative electrode plate, and the porous membrane is either encapsulated by the negative electrode plate in which the fiber pad is integrated, or encapsulated by the adjacent positive electrode plate; or The negative electrode plate is encapsulated by a ribbed porous membrane, while a fiber pad is located between the encapsulated negative electrode plate and the porous membrane encapsulating the negative electrode plate.

6. A battery comprising: An electrode array comprising one or more negative electrodes and one or more positive electrodes interposed between the one or more negative electrodes; Fiber pad encapsulation, wherein one of the one or more negative electrodes is disposed; and A porous membrane encapsulation, which includes a fiber pad encapsulation.

7. The battery as claimed in claim 6, wherein, The fiber pad encapsulation is one of nonwoven materials, mesh, fleece, and combinations thereof; The fiber pad encapsulation comprises at least one material selected from glass fiber, pulp, polymer, and combinations thereof; The fiber pad encapsulation is formed from a polymer and one or more of the polymer with additional glass fibers, pulp, and combinations thereof; The fiber pad encapsulation comprises at least one material selected from glass fiber, pulp, polymer, and combinations thereof, wherein the polymer comprises one or more materials selected from polyolefin, polyester, polyamide, polyimide, and combinations thereof; The fiber pad encapsulation comprises an inorganic material; the inorganic material comprises silicon dioxide; The fiber pad encapsulation comprises a spunbond melt nonwoven composite material; the fiber pad encapsulation comprises a carbon fiber nonwoven material; The carbon fiber nonwoven material and / or the fiber pad encapsulation include: conductive carbon, graphite, artificial graphite, activated carbon, acetylene black, carbon black, high surface area carbon black, graphene, high surface area graphene, Keitjen black, carbon fiber, carbon filament, carbon nanotube, open-cell carbon foam, carbon pad, carbon felt, carbon buckminster fullerene (buckminster ball), flake graphite, carbon oxide, and combinations thereof; The fiber pad encapsulation includes a nucleating additive; the nucleating additive is one of carbon, barium sulfate (BaSO4), or combinations thereof; The carbon forms include conductive carbon, graphite, artificial graphite, activated carbon, carbon paper, acetylene black, carbon black, high surface area carbon black, graphene, high surface area graphene, Keitjen black, carbon fiber, carbon filament, carbon nanotubes, open-cell carbon foam, carbon pads, carbon felt, carbon buckminster fullerene (buckminster balls), aqueous carbon suspension, sheet graphite, carbon oxide, and combinations thereof. The fiber pad encapsulation includes a conductive layer disposed adjacent to the negative electrode; the conductive layer includes conductive carbon, graphite, artificial graphite, activated carbon, carbon paper, acetylene black, carbon black, high surface area carbon black, graphene, high surface area graphene, Keitjen black, carbon fiber, carbon filament, carbon nanotube, open-cell carbon foam, carbon pad, carbon felt, carbon buckminster fullerene (buckminster ball), aqueous carbon suspension, sheet graphite, carbon oxide, and combinations thereof; The porous membrane includes one or more sets of ribs on at least one of its surfaces; the one or more sets of ribs are on two of its surfaces. The ribs in one or more sets of ribs have a height of about 10 μm to about 2.0 mm; The porous membrane comprises at least one material selected from natural materials, synthetic materials, polyolefins, phenolic resins, polyvinyl chloride (PVC), natural rubber, synthetic rubber, synthetic wood pulp, glass fiber, lignin, cellulose fiber, and combinations thereof; The porous membrane comprises polyethylene, silica, and processing oil; The porous membrane is sealed on one of the following: one side of the positive electrode, both sides of the positive electrode, and three sides of the positive electrode; The fiber pad encapsulation is sealed on one of the following: one side of the negative electrode, both sides of the negative electrode, and three sides of the negative electrode; The porous membrane has a porosity greater than about 55%, greater than about 60%, or greater than about 65%; and / or The porous membrane is a microporous battery separator.

8. A battery comprising: An electrode array comprising one or more negative electrodes and one or more positive electrodes interposed between the one or more negative electrodes; One or more electrode and fiber pad assemblies, including a fiber pad that is at least partially integrated into at least one of the one or more negative electrodes; and A porous membrane that encapsulates one of the one or more electrode and fiber pad assemblies, or at least one of the one or more positive electrodes adjacent to the one or more electrode and fiber pad assemblies.

9. The battery as claimed in claim 8, wherein, The battery further includes an active material attached to the one or more negative electrodes; The fiber pad is integrated into the active material at a ratio of about 2% to about 50%, about 5% to about 25%, about 5% to about 20%, or about 10% to about 15% of the fiber pad thickness; The fiber mat is one of nonwoven materials, mesh, fleece, and combinations thereof; The fiber mat is formed of at least one material selected from glass fiber, pulp, polymer, and combinations thereof; The fiber mat is formed from a polymer and the polymer together with one or more additional materials selected from glass fiber, pulp and combinations thereof; The polymer includes at least one selected from polyolefins, polyesters, polyamides, polyimides, and combinations thereof; The fiber mat comprises inorganic materials; the inorganic materials include silicon dioxide. The fiber pad is a spunbond melt nonwoven composite material; The fiber pad is a carbon fiber nonwoven material; The carbon fiber nonwoven material and / or the fiber mat include: conductive carbon, graphite, artificial graphite, activated carbon, acetylene black, carbon black, high surface area carbon black, graphene, high surface area graphene, Keitjen black, carbon fiber, carbon filament, carbon nanotube, open-cell carbon foam, carbon mat, carbon felt, carbon buckminster fullerene (buckminster ball), sheet graphite, carbon oxide, and combinations thereof; The fiber pad contains nucleating additives; and / or The nucleating additive is one of carbon, barium sulfate (BaSO4), or combinations thereof.

10. A battery or accumulator comprising: A fiber pad encapsulation, wherein one of one or more negative electrodes is provided; and A porous membrane encapsulation, including a fiber pad encapsulation, wherein... The negative electrode comprises a negative electrode active material inserted into the gaps and micropores of the fiber pad to form a mixture layer integrated with the negative electrode active material, the mixture layer covering 2% to 50% of the thickness of the fiber pad; additionally, The fiber pad encapsulation is one of nonwoven materials, mesh, fleece, and combinations thereof; The fiber pad encapsulation is formed from a polymer and one or more of the polymer together with additional glass fibers, pulp, and combinations thereof; and the polymer includes one or more materials selected from polyolefins, polyesters, polyamides, polyimides, and combinations thereof; The fiber pad encapsulation comprises an inorganic material; the inorganic material comprises silicon dioxide; The fiber pad encapsulation comprises a spunbond melt nonwoven composite material; The fiber pad encapsulation comprises carbon fiber nonwoven material; the carbon fiber nonwoven material and / or the fiber pad encapsulation comprises: conductive carbon, graphite, artificial graphite, activated carbon, acetylene black, carbon black, high surface area carbon black, graphene, high surface area graphene, Keitjen black, carbon fiber, carbon filament, carbon nanotubes, open-cell carbon foam, carbon pad, carbon felt, carbon buckminster fullerene (buckminster balls), flake graphite, carbon oxide, and combinations thereof; and / or The fiber pad is encapsulated and attached to both sides of the negative electrode.

11. The battery or accumulator as claimed in claim 10, wherein, The fiber pad encapsulation includes a conductive layer disposed adjacent to the negative electrode; the conductive layer comprises conductive carbon, graphite, artificial graphite, activated carbon, carbon paper, acetylene black, carbon black, high surface area carbon black, graphene, high surface area graphene, Keitjen black, carbon fiber, carbon filament, carbon nanotube, open-cell carbon foam, carbon pad, carbon felt, carbon buckminster fullerene (buckminster ball), aqueous carbon suspension, sheet graphite, carbon oxide, and combinations thereof. The porous membrane includes one or more sets of ribs on at least one surface thereon; the one or more sets of ribs are on two surfaces thereon; the ribs in the one or more sets of ribs have a height of about 10 μm to about 2.0 mm; The porous membrane comprises at least one material selected from natural materials, synthetic materials, polyolefins, phenolic resins, polyvinyl chloride (PVC), natural rubber, synthetic rubber, synthetic wood pulp, glass fiber, lignin, cellulose fiber, and combinations thereof; The porous membrane comprises polyethylene, silica, and processing oil; The porous membrane is attached to both sides of the positive electrode; The porous membrane has a porosity of greater than 55%, greater than 60%, or greater than 65%. The porous membrane is a microporous battery separator; The porous membrane is attached to three sides of the positive electrode, or the porous membrane is attached to three sides of one or more electrodes and fiber pad assemblies; The porous membrane includes ribs on one or more of its surfaces; The fiber pad is disposed within the encapsulation; The ribs have a height of 10 μm to 2.0 mm, 5 μm to 300 μm, or 5 μm to 200 μm; The fiber pad has a thickness of 50% to 150% of the rib height; The porous membrane has ribs on both of its surfaces, or the porous membrane contains processing oil in an amount of about 5% to about 15% of the weight of the porous membrane; and / or The system includes a vehicle and a battery, wherein the vehicle is selected from the following: automobiles, trucks, motorcycles, all-terrain vehicles, motorcycles, forklifts, golf carts, hybrid vehicles, hybrid electric vehicles, electric vehicles, idle start-stop (ISS) vehicles, electric rickshaw batteries, electric tricycles, electric bicycles, wheelchairs, and ships.

12. A separator for a battery or accumulator, comprising a polyolefin microporous membrane, wherein: Polyethylene, fillers, and processing oils; The polyolefin microporous membrane further comprises at least one of the following: The filler is silica filler, and its content, by weight, is 40% of the membrane. Polyolefin microporous membranes are flat sheets, or membranes with ribs or other protrusions on one or both sides; The partition is further compressed using a machine press or calender roll group or rollers; The filler includes one of the following, selected from: silica, dry-processed fine silica, precipitated silica, amorphous silica, alumina, talc, fish meal, fish bone meal, and combinations thereof; The partition has a final processed oil content of less than about 20%, between about 14% and 20%, less than 19%, 18%, 17%, 16%, 15%, 14%, 13%, 12%, 11%, 10%, 9%, 8%, 7%, 6% or 5% by weight; The microporous membrane comprises nucleating additives and / or a coating on the microporous membrane; the coating is or includes carbon, such as conductive carbon, graphite, artificial graphite, activated carbon, carbon paper, acetylene black, carbon black, high surface area carbon black, graphene, high surface area graphene, Keitjen black, carbon fiber, carbon filament, carbon nanotube, open-cell carbon foam, carbon pad, carbon felt, carbon buckminster fullerene (buckminster ball), aqueous carbon suspension, and combinations thereof. The microporous membrane, comprising additives and / or a carbon paper coating, is a fabric or non-fabric material, disposed between the separators and in close contact with the separators; and The battery separator has a strength of less than or equal to 65 mΩ·cm. 2 Resistance (ER) less than or equal to 50 mΩ·cm 2 The resistance (ER) is 35 mΩ·cm or less. 2 The resistance (ER).

13. A separator for a battery or accumulator, comprising: The first rib array extends from the first side of the back net; The second rib array extends from the second side of the back net; Both the first rib array and the second rib array are ribs that span the machining direction (CMD). At least one of the first rib array and the second rib array has a siliceous material between its ribs, the siliceous material being selected from one or more of the following: precipitated silica, dry-processed fine silica, amorphous silica, fumed silica, granulated silica, and dispersed silica. Alternatively, it may also have at least one of the following features: The thickness of the back mesh ranges from 100 micrometers to 400 micrometers; At least one of the first rib array and the second rib array includes individual ribs of different heights; one or both of the first rib array and the second rib array include non-continuous ribs. The battery separator is a filled polyolefin battery separator; The content of rubber, rubber derivatives, latex, or latex derivatives in the battery separator is 1% to 3%. The partition is a slice, sleeve, covering, or encapsulation partition; The partition is a covering or enclosing partition with one or more slits at the bottom; The battery separator includes a surfactant, selected from one or more of ionic surfactants, nonionic surfactants, and amphoteric surfactants; The total thickness of the battery separator is between 600 micrometers and 1100 micrometers; The discontinuous ribs are inclined discrete ribs; The discontinuous ribs are acid-mixed ribs; The ratio of silica filler to polyolefin is 2.5:1 to 5:1; The oil content of the battery separator is 5% to 20%; The aniline point of the oil is 80°C to 125°C; The battery separator contains carbon on at least one of the first and second sides; The battery separator contains one or more of the following in the interrib space on at least one of the first and second sides: precipitated silica, dry-processed fine silica, amorphous silica, fumed silica, granulated silica, dispersed silica, alumina, talc, superabsorbent resin, and fish bone powder; and / or Their combination.

14. A battery capable of suppressing acid stratification when operating in a partially charged state, wherein, The tensile strength of its fiber pad in the processing direction is 200N / 50mm, while the tensile strength across the processing direction is 150N / 50mm.

15. A battery capable of suppressing acid stratification when operating in a partially charged state, wherein, The silanol group transforms the silicon dioxide structure from a crystalline structure to an amorphous structure.

16. A battery capable of suppressing acid stratification when operating in a partially charged state, wherein, A shish-kebab structure is formed within the polyolefin.